Kathryn Dyt. The Nature of Kingship: The Weather-World in Nineteenth-Century Vietnam. Honolulu: University of Hawai‘i Press, 2025. - Thompson, C. Michele (Southeast Asian Studies, 2026)
Keywords: book.review; dept.his

British first world war propaganda: from A to Z - Paddock, Troy (First World War Studies, 2026)
Keywords: dept.his

Melissa Reynolds. Reading Practice: The Pursuit of Natural Knowledge from Manuscript to Print - Petto, Christine (The American Historical Review, 2025)
Keywords: Knowledge production; Knowledge-based systems; Natural (archaeology); Traditional knowledge; dept.his

Meredith L. McCoy. On Our Own Terms: Indigenous Histories of School Funding and Policy - Amerman, Steve (The American Historical Review, 2025)
Keywords: Indigenous; Indigenous culture; dept.his

Bamboo in Vietnam: an anthropological and historical approach, written by ðinh Trọng Hiếu and Emmanuel Poisson - Thompson, C. (East Asian Science Technology and Medicine, 2025)
Keywords: Ancient history; Anthropology; Archaeology; Asian studies; Bamboo; Biology; Botany; China; History; Medicine; Sociology; Traditional medicine; dept.his

Finding the Sweet Spot: Wild Bees, Indigenous Peoples, and the Historic Trade in Honey and Beeswax in Northern Vietnam - Thompson, C. Michele (Asian Medicine, 2026)
When most people think of the use of animals in traditional systems of medicine, what springs to mind is one kind or another of megafauna such as rhinoceros, bears, sharks, and others. Sometimes more mundane creatures such as pangolins are included. However, invertebrates and substances produced by them have been used in Asian systems of medicine since the earliest records of materia medica from the region were created. Animals used range from shellfish and crustaceans to various insects and insect products such as cocoons, honey, and beeswax. In terms of their role in the food chain, and as pollinators, invertebrates are as crucial to the health, indeed the survival, of ecosystems in Asia and elsewhere as are megafauna. Loss and degradation of habitat is probably affecting more invertebrates than medicalization. Still, the expansion of medicalization in Asia and beyond is contributing to the danger many populations of invertebrates currently face. This article gives an overview of the place of invertebrates in Vietnamese traditional medicine and then presents a case study of two varieties of honey- and beeswax-producing bees found in northern mainland Southeast Asia and southern China: Apis dorsata F. and Apis cerana. © C. Michele Thompson, 2026. Published with license by Koninklijke Brill BV
Keywords: Arthropod; Asian traditional medicine; Creatures; Habitat; Invertebrate; Mainland; Mainland China; Southeast asia; Vietnamese; Vietnamese medicine; bees; beeswax; dept.his; ecological damage; endangered species; honey; invertebrates

‘A small measure of fairness’: Black South Africans and the Courts, 1919–1938 - Eastman, Michael; Feinberg, Harvey (Journal of Southern African Studies, 2025)
Keywords: Computer science; Measure (data warehouse); Political science; Sociology; South Africa; administration of justice; appeals; courts; criminal justice; dept.his; judges; justice for Africans; magistrates; reviews

Defining the enemy: Propaganda in a civil war - Paddock, Troy (Violence and Propaganda in European Civil Wars, 2025)
Propaganda in the first half of the 20th century is usually associated with the atrocity stories from World War I and the anti-Semitic propaganda of the Nazi regime and World War II. This chapter provides a brief overview of the history of propaganda and propaganda theory before turning its attention to a theory of propaganda in civil war. It argues that what makes propaganda in a civil war unique is that it is a combination of both political and war propaganda. Current research on propaganda theory emphasizes that propaganda is in service of an ideology and focuses on propaganda as disseminating information that tries to avoid reason and veracity. The chapter argues that propagandists in a civil war setting are presenting the ‘truth’ as they understand it. Informed by Carl Schmitt’s “friend/enemy” distinction in his Concept of the Political, the author argues that each side argued and was convinced that they represented the values and interests of the nation and its people, and that because the stakes of the conflict were so high that all actions could be justified.
Keywords: dept.his

Changing Working Environments in Philosophy: Reflections from a Case Study - McConwell, Alison; Bogacz, Magdalena; Brecevic, Char; Haber, Matthew; Wu, Jingyi; Roe, Sarah (Philosophy of Science, 2025)
Abstract There is an “underrepresentation problem” in philosophy departments and journals. Empirical data suggest that while we have seen some improvements since the 1990s, the rate of change has slowed down. Some posit that philosophy has disciplinary norms making it uniquely resistant to change. We present results from an empirical case study of a philosophy department that achieved and maintained male-female gender parity among its faculty as early as 2014. Our analysis extends beyond matters of gender parity because that is only one, albeit important, dimension of inclusion. We build from the study to reflect on strategies that may catalyze change.
Keywords: Computer science; Epistemology; Philosophy; Sociology; dept.his; peer-reviewed

How the west was run: Local government in Late Roman Italy - McCunn, Stuart (Late Roman Italy: Imperium to Regnum, 2023)
h4Explores the major political, social, economic, religious and cultural changes impacting what was once the most important region of the Roman world/h4ulliThe first modern research volume on a core region of Late Antiquity/liliA tight and distinctly chronological focus on the second quarter of the first millennium CE, that allows for a different vision of the many vicissitudes of Late Roman Italy, among other works on Ancient and Late Antique Italy./liliAn emphasis on one of the key features of Late Antiquity: the transformation of the Roman Empire in the West into successor polities./liliA balanced range of topics, including ones rarely encountered in this type of work (such as gender or environmental history), with a special focus on political transformation and violence./li/ulpThis research volume reassesses one of the most fundamental transformations in Late Antiquity, centered on a pivotal region: the transition from ‘Empire’ to ‘Kingdom’ in Italy c. 250-500. During the first quarter of the first millennium, Italy was still the heart of the Roman Empire; the only political superstructure ever managing to encompass the entire Mediterranean world and its European hinterland. Yet during the second quarter of this millennium, Italy underwent dramatic evolutions from demotion to a provincialized region (c. 285-395), to a new imperial hub kept afloat by cannibalizing other provinces’ resources (c. 395-476), to an autonomous regnum governed by non-Roman rulers as part of an Eastern Roman ‘Commonwealth’ (c. 475-535)./p
Keywords: dept.his

Matthew Fontaine Maury: Pathfinder - Smith, Jason W (International Journal of Maritime History, 2016)
Historians have long recognized Matthew Fontaine Maury as an important if controversial figure in the histories of science and of maritime and naval affairs. These assessments, however, rest on scholarship that is by now more than a half-century old. It is therefore appropriate to look at Maury’s significance from fresh perspectives, incorporating recent historiographical trends in the history of science and cartography, environmental history, cultural history and military history. This article focuses on the ways in which Maury’s cartographic work reframed mariners’ understanding of the marine environment away from what he perceived to be a watery wilderness towards an ordered environment safe and favourable to American commerce. Maury was long known as ‘The Pathfinder of the Seas’, but I argue that his significance, in fact, lies in the ways he and his staff at the Naval Observatory organized the sea as a ‘common highway’, tracing paths, but also imposing narratives and constructing new meanings. Maury’s tool was the nautical chart and, particularly, his Wind and Current Charts series that by the 1850s reimagined the ways mariners, navigators and naval officers understood and harnessed the ocean environment. The article briefly considers these charts from three perspectives – method, process and representation – in order to see the ways in which Maury was pushing the boundaries of the cartographic medium to usher in revolutionary ways of envisioning the ocean environment. By quantifying winds, symbolizing whales and infusing the sea with ship tracks, among other things, Maury was imposing potent, if sometimes flawed, new ways of understanding and imagining the sea that were central to American maritime expansion in the antebellum era. In this and other ways, we can see Maury anew, a figure central to the growth of American commercial empire and to new ways of understanding and thinking about the sea.
Keywords: dept.his

Painting on a White Foundation: Color, Countenance, and Performance in the Analects and Han Feizi - Radice, Thomas (From Surface to Meaning: Analyzing via Color)
Looking at colour can be a way not only to think within or about culture but also to probe the boundaries of cultural approaches. The "Cultural Turn," as it has been called, has made an impact across disciplines. In history, it replaced long-established explanatory models provided by Marxism and modernisation theory. Even fields like art history and literature, which always considered themselves allied to the arts rather than to the sciences, were reshaped by new understandings of culture - for instance, as a much larger system of meaning in which the works they studied were a part. But "culture" is notoriously murky, and its analytical use can obfuscate patterns of causality. This volume analyses how looking at colour can take us further.
Keywords: dept.his

Community and identity in Castilian histories of the fifteenth century - Kern, Darcy (Sharq al-Andalus, 2021)
La historia fue tan importante para la construcción de la identidad comunitaria y la legitimidad política en el siglo XV como lo es hoy, y en los reinos de España igualmente tenso. Los cronistas y biógrafos católicos castellanos parecen inseguros del estado preciso de los moros en Iberia. Todos estaban de acuerdo con el control político o el señorío de los cristianos castellanos, pero pocos tenían una idea clara de las implicaciones de ese señorío para los moros. ¿Debería permitirse a los moros permanecer como parte de la comunidad una vez que un monarca cristiano castellano tomara el control de su ciudad, región o reino, o no había posibilidad de que pertenecieran? Rodrigo Sánchez de Arévalo (1404-1470), Fernán Pérez de Guzmán (c. 1377-c. 1460), Alonso Fernández de Palencia (1423-1492), Hernando de Pulgar (1436-c. 1492), y Mosén Diego de Valera (1412-1488) dieron diferentes respuestas. Todos coincidieron en que la comunidad castellano-leonesa existía antes de al-Andalus y, por lo tanto, era la comunidad política legítima de Hispania. La mayoría de ellos aceptaron la presencia de Granada de facto pero no de jure. Sin embargo, Arévalo, Valera y Pulgar sugieren la posibilidad de una comunidad política musulmana de jure bajo dominio castellano; Palencia y Guzmán no.
Keywords: dept.his

Umayyad Caliphate - Judd, Steven C. (The Encyclopedia of Empire, 2016)
The Umayyad Caliphate (661–750) was the first Islamic dynasty. Muʿawiya ibn Abi Sufyan established himself as caliph in Damascus after his victory over ʿAli ibn Abi Talib in the civil war that followed the murder of ʿUthman ibn ʿAffan in Medina. Muʿawiya and his successors expanded the territory under Muslim rule dramatically. At their peak, the Umayyads ruled an empire stretching from Spain to the frontiers of China and India. The Umayyads made significant contributions to the development of the Islamic faith and to the spread of the Arabic language throughout the region. Dynastic crises, revenue shortfalls, and the limitations of an empire based on conquest ultimately led to their demise at the hands of the Abbasids in 750.
Keywords: 6th–10th centuries; Islam; Late Antiquity; Western Asia; dept.his; history; northern Africa; religious history

A Fantasy in Fashion: African American Empowerment in an Era of Opulence - Carter-David, Siobhan; Wu, Ellen (Race and Retail: Consumption across the Color Line, 2015)
Race has long shaped shopping experiences for many Americans. Retail exchanges and establishments have made headlines as flashpoints for conflict not only between blacks and whites, but also between whites, Mexicans, Asian Americans, and a wide variety of other ethnic groups, who have at times found themselves unwelcome at white-owned businesses.  Race and Retail documents the extent to which retail establishments, both past and present, have often catered to specific ethnic and racial groups. Using an interdisciplinary approach, the original essays collected here explore selling and buying practices of nonwhite populations around the world and the barriers that shape these habits, such as racial discrimination, food deserts, and gentrification. The contributors highlight more contemporary issues by raising questions about how race informs business owners’ ideas about consumer demand, resulting in substandard quality and higher prices for minorities than in predominantly white neighborhoods.  In a wide-ranging exploration of the subject, they also address revitalization and gentrification in South Korean and Latino neighborhoods in California, Arab and Turkish coffeehouses and hookah lounges in South Paterson, New Jersey, and tourist capoeira consumption in Brazil.   Race and Retail illuminates the complex play of forces at work in racialized retail markets and the everyday impact of those forces on minority consumers. The essays demonstrate how past practice remains in force in subtle and not-so-subtle ways.
Keywords: dept.his

Ritual performance in early Chinese thought: A dramaturgical perspective - Radice, T. (Ritual Performance in Early Chinese Thought: A Dramaturgical Perspective, 2024)
Examining early Chinese ritual discourse during the Warring States and early Western Han Periods, this book reveals how performance became a fundamental feature of ritual and politics in early China. Through a dramaturgical lens, Thomas Radice explores the extent to which performer/spectator relationships influenced all aspects of early Chinese religious, ethical, and political discourse. Arguing that the Confucians conceived ritual as primarily a dramaturgical matter, this book demonstrates not only that theatricality was necessary for expression and deception in a community of spectators, but also how a theatrical 'presence' ultimately became essential to all forms of public life in early China. Thomas Radice illuminates previously unexplored connections between early Chinese texts, aesthetics, and traditions. © Thomas Radice, 2025. All rights reserved.
Keywords: dept.his

Englishing Paolo Sarpi and gelding the Pope in England, 1606−1620 - Kern, Darcy (The Seventeenth Century, 2024)
An important reason for the success of the Venetian Paolo Sarpi’s ideas in England is found in the ‘Englishing’ of his printed works, that is, their adaptation and appropriation by printers and translators. During the Venetian interdict (c. 1606–1608), Sarpi’s tracts were treated as timely, informative, and politically useful news. Englishing consisted of re-writing titles by adding bombastic phrases, changing printers’ ornaments, and adding marginalia to help readers unfamiliar with Italy. In the History of the Council of Trent, published in 1619 (Italian) and 1620 (English), the Englishing became more substantive – adding lengthy prefaces, inserting words into Sarpi’s text, and including the translator’s name. The prefaces framed the book’s contents, while the translator’s name provided authority. The additional words made the English History even more partisan than the Italian Historia. Publishers and translators modified Sarpi’s works to produce aggressive readings that diverged from his own political and religious goals.
Keywords: Catholic Church; Church of England; England; Translation; Venice; dept.his; peer-reviewed; print culture

Receiving more: Utopia in Spain and new Spain - Kern, D. (The Oxford Handbook of Thomas More's Utopia, 2023)
Keywords: dept.his

Book Review: Chinese in the Post-Civil War South; a People Without a History - Thompson, C Michele (The Southern Historian, 1985)
Keywords: book.review; dept.his

Book Review: The Vaccinators: Smallpox, Medical Knowledge, and the 'Opening' of Japan - Thompson, C Michele (EASTM: East Asian Science, Technology and Medicine, 2013)
Keywords: book.review; dept.his

Vietnam - Thompson, C Michele (Acquiring Cross-Cultural Competence: Four Stages for Students of French vol I., 1998)
Keywords: dept.his

Tuệ Tĩnh 1330-?" - Thompson, C Michele (Dictionary of Medical Biography, 2007)
Keywords: dept.his

Lán Ông 1721-1791? - Thompson, C Michele (Dictionary of Medical Biography, 2007)
Keywords: dept.his

Tuệ Tĩnh Vietnamese Monk-Physician at the Ming Court - Thompson, C Michele (The Illustrated History of Chinese Medicine and Healing, 2013)
Keywords: dept.his

French Colonial Medicine and Pharmacology in Cambodia, Laos and Vietnam, 1802-1954" - Thompson, C Michele (Science Across the European Empires, 1800-1950, 2005)
Keywords: dept.his

Scripts and Medical Scripture in Vietnam: Nôm and Classical Chinese in the Historic Transmission of Medical Knowledge in Pre-Twentieth Century Vietnam - Thompson, C Michele (Nghiên cứu Chữ Nôm (Research on Nôm Script), 2006)
Keywords: dept.his

Book Review: Chinese Acupuncture [l'Acuponcture Chinoise: La Tradition chinoise classifiée, precisée]. (Paris: Maloine, 1972). By George Soulié de Morant. Translated by Lawrence Grinnell, Claudy Jeanmougin and Maurice Leveque. Edited by Paul Zmiewski. Brookline, Mass.: Paradigm Publications, 1994. xxxii, 896 pp. $125.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800040171/resource/name/firstPage-S0021911800040171a.jpg
Keywords: book.review; dept.his

Book Review: Sexual Attraction and Childhood Association: A Chinese Brief for Edward Westermarck. By Arthur P. Wolf. Stanford, Calif.: Stanford University Press, 1995. xxiii, 561 pp. $65.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002191180002934X/resource/name/firstPage-S002191180002934Xa.jpg
Keywords: book.review; dept.his

Book Review: Essays Into Vietnamese Pasts. Edited by K. W. Taylor and John K. Whitmore. Ithaca, N.Y.: Southeast Asia Program, Cornell University Press, 1995. 288 pp. $20.00 (paper). - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800029971/resource/name/firstPage-S0021911800029971a.jpg
Keywords: book.review; dept.his

Book Review: Beyond the Bronze Pillars: Envoy Poetry and the Sino-Vietnamese Relationship (review) - Thompson, Claudia Michele (China Review International, 2006)
Keywords: book.review; dept.his

Review of Views of Seventeenth-Century Vietnam: Christoforo Borri on Cochinchina and Samuel Baron on Tonkin - Thompson, C. Michele (Crossroads: An Interdisciplinary Journal of Southeast Asian Studies, 2007)
Keywords: book.review; dept.his

Review of Cult, Culture, and Authority: Princess Liễu Hạnh in Vietnamese History - Thompson, Michele (Journal of Vietnamese Studies, 2008)
Keywords: book.review; dept.his

Book Review: Aro Velmet, Pasteur’s Empire: Bacteriology & Politics in France, Its Colonies, & the World (New York: Oxford University Press, 2020), pp. xiv + 306, $78.00, hardback, ISBN: 9780190072827. - Thompson, C. Michele (Medical History, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0025727321000508/resource/name/firstPage-S0025727321000508a.jpg
Keywords: dept.his

Book Review: Edington, Claire E. – Beyond the Asylum: Mental Illness in French Colonial Vietnam. - Thompson, C. Michele (Histoire sociale / Social History, 2023)
Keywords: book.review; dept.his

Book Review: Epidemic Politics in Contemporary Vietnam: Public Health and the State By Martha Lincoln, London: Bloomsbury Academic. 2022. 232 pp.1 - Thompson, C. Michele (Medical Anthropology Quarterly, 2024)
Keywords: book.review; dept.his

Book Review: Fragrant Frontier: Global Spice Entanglements from the Sino-Vietnamese Uplands - Thompson, C. Michele (Agricultural History, 2024)
The editors of Fragrant Frontier have produced an impressively researched book on the contemporary growers, in northern Vietnam and Southwest China, of three spices—star anise, black cardamom, and cinnamon, each of which has local, regional, and international economic importance—as well as the human links in the global commodity chain of these spices. This volume is much more coherent than many edited volumes, and readers should not skip any of it, as there are nice little surprises waiting here and there in the text.A good example is the “Preface and Acknowledgements” section, as this not only provides interesting information on how the volume came into being but also links to websites and scannable QR codes for “story maps” on the three spices and the places mentioned in the rest of the volume. This is a nice touch that gives this volume about the recent situation of farmers, local traders, marketplace workers, street vendors (of both the spices and foods prepared with them), wholesalers, exporters, and state officials a very contemporary feel. These story maps are only the first of an extensive number of relevant, well-done, and well-used illustrations including photographs, maps, and tables inserted throughout the following chapters.
Keywords: book.review; dept.his

Scripts, Signs, and Swords: The Việt Peoples and the Origin of Nôm - Thompson, Claudia Michele (2000)
Keywords: dept.his

Mission to Macau: smallpox, vaccinia, and the Nguyen dynasty - Thompson, C. Michele (Portuguese studies review, 2001)
Keywords: dept.his

Medicine, Nationalism, and Revolution in Vietnam: the Roots of a Medical Collaboration to 1945 - Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2003)
Keywords: dept.his

Jean Marie Despiau: Unjustly Maligned Physician in the Medical Service of the Nguyen - Thompson, C. Michele (Vietnam and the West, 2010)
Keywords: dept.his

Setting the stage: Ancient medical history of the geographic space that is now Vietnam - Thompson, C. Michele (Southern Medicine for Southern People: Vietnamese Medicine in the Making. Newcastle upon Tyne: Cambridge Scholars Publishing, 2012)
Keywords: dept.his

The Nguyễn Initiative to Acquire Vaccinia, 1820-1821 - Thompson, C. Michele (Global Movements, Local Concerns: Medicine and Health in Southeast Asia, 2012)
Keywords: dept.his

Introduction from the Guest Editor: Forays into the Field of Vietnamese Military Technology - Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2003)
Keywords: dept.his

Swarms, Herds, and Peoples: Examinations of Interspecies Dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
Gale OneFile includes Swarms, Herds, and Peoples: Examinations of Interspecie by David A. Bello and C. Michele Thompson. Click to explore.
Keywords: dept.his

Fighting for health: medicine in cold war Southeast Asia - Thompson, Claudia Michele; Sweet, Kathryn; Aso, Michitake (History of medicine in Southeast Asia series, 2024)
Keywords: 20th century; Cold War; Medicine; 20th century; Medical care; 20th century; Medical policy; History; History; Public Health; Public health; Southeast Asia; dept.his; history; Health Policy; history; History of Medicine; Southeast Asia; Asia, Southeastern

The Duke of Lennox, 1574 1624: A Jacobean Courtier s Life. David Bergeron. Edinburgh: Edinburgh University Press, 2022. x + 244 pp. $110 - Kern, Darcy (Renaissance Quarterly, 2023)
Keywords: book.review; dept.his

The many currents of antebellum maritime empire - Smith, Jason W. (Diplomatic History, 2023)
Keywords: dept.his; peer-reviewed

Costa Rica after Coffee: The Co-op Era in History and Memory - Kordick, Carmen (Agricultural History, 2023)
Keywords: book.review; dept.his

Al-Ḥağğāğ b. Yūsuf and the Umayyad Qurʾān in Syrian Historiography - Judd, Steven C. (Archimède. Archéologie et histoire ancienne, 2023)
Keywords: dept.his; peer-reviewed

Aspects of Greek-Russian Relations in the Early Modern and Modern Periods (17th-20th Centuries) - Chrissidis, Nikolaos (Annuaire de l'École pratique des hautes études (EPHE), Section des sciences religieuses. Résumé des conférences et travaux, 2023)
This series of four presentations sought to examine case studies of Greek-Russian relations in the early modern and, mostly, modern period. In the choice of topics, I was guided by two considerations: first, I sought to highlight topics that, to my mind, have not yet attracted the attention they deserve in historiography. For example, although alms collections in the Russian Empire in the early modern period have been discussed repeatedly, this has not been the case until quite recently for t...
Keywords: Christianisme orthodoxe; Histoire des chrétiens d’Orient (XVIe-XXIe siècle); dept.his

Russia in the German global imaginary: imperial visions and utopian desires, 1905-1941 - Paddock, Troy (First World War Studies, 2023)
Keywords: book.review; dept.his

Review of Chivalry and Violence in Late Medieval Castile, by Samuel A. Claussen - Kern, Darcy (Journal of Military History, 2022)
Keywords: book.review; dept.his; ⛔ No DOI found

Parliament in print: William Caxton and the history of political government in the fifteenth century - Kern, Darcy (Journal of Medieval History, 2014)
This article explores the narrative of parliamentary history in fifteenth-century England, specifically as found in the texts William Caxton printed. It investigates Caxton's approach to history and motivation for choosing texts, his translations and vocabulary, his editorial oversight and his audience. As his confidence in his own skill grew, and as he moved from a continental to an English context, his reading of parliaments changed. Initially it corresponded to his French texts, but by the early 1480s he understood the term ‘parliament’ to mean some variation of the contemporary English Parliament. Caxton's later understanding is reflected in the histories he published. This article emphasises the importance of Caxton's historical narratives to Parliament's legitimacy and to political discourse in a time when few parliaments were held.
Keywords: England; William Caxton; dept.his; history; legitimacy; parliament; peer-reviewed; print

al-Awza'i and Umayyad Influence on Islamic Legal Development - Judd, Steven (The Umayyad World, 2020)
The Umayyad World encompasses the archaeology, history, art, and architecture of the Umayyad era (644–750 CE). This era was formative both for world history and for the history of Islam. Subjects covered in detail in this collection include regions conquered in Umayyad times, ethnic and religious identity among the conquerors, political thought and culture, administration and the law, art and architecture, the history of religion, pilgrimage and the Qur’an, and violence and rebellion. Close attention is paid to new methods of analysis and interpretation, including source critical studies of the historiography and inter-disciplinary approaches combining literary sources and material evidence. Scholars of Islamic history, archaeologists, and researchers interested in the Umayyad Caliphate, its context, and infl uence on the wider world, will find much to enjoy in this volume.
Keywords: dept.his

Siyar: An Ephemeral Genre of Islamic Legal Literature? - Judd, Steven (Islam on the Margins, 2022)
Keywords: History & Culture; Middle East and Islamic Studies; Religion in Asia; Religious Studies; dept.his

Islam on the Margins: Studies in Memory of Michael Bonner - Judd, Steven; Haug, Robert (BRILL, 2023)
Islam on the Margins commemorates the contributions Michael Bonner made to Near Eastern Studies. It consists of fourteen contributions by his students and colleagues that focus on various aspects of his work. The contributions coalesce around four major themes of Bonner’s endeavours: Holy War and the Frontier, Qurʾan and Law, Geography and Ethnography, and Books, Coins and Titles. Collectively, the contributions underscore the breadth of Michael Bonner’s erudition and impact on the field.
Keywords: History / Asia / General; History / Middle East / General; Religion / Islam / General; dept.his

'Abd al-Rahman b. 'Amr al-Awza'i - Judd, Steven C. (Simon and Schuster, 2019)
‘Abd al-Rahman b. ‘Amr al-Awza‘i (c.707–774) was Umayyad Syria’s most influential jurist, part of a generation of scholars who began establishing the first formal structures for the preservation and dissemination of religious knowledge. Following the Abbasid revolution, they provided a point of stability in otherwise unstable times. Despite his close ties to the old regime, al-Awza‘i continued to participate in legal and theological matters in the Abbasid era. Although his immediate impact would prove short-lived, his influence on aspects of Islamic law, particularly the laws of war, endures to this day.
Keywords: Biography & Autobiography / Historical; History / General; History / Middle East / General; Law / Islamic; Religion / History; Religion / Islam / General; Religion / Islam / Theology; Social Science / Islamic Studies; dept.his

The Cassock Does Not a Monk Make. Or Does It? Fake and Real Monks from the Orthodox East in the Russian Empire (19th — Early 20th Сentury) - Chrissidis, Nikolaos (Istoriya, 2023)
Monastic tonsure of citizens of the Russian Empire abroad became a particularly complex issue during the latter half of the nineteenth century, when Mt. Athos became a favorite destination of those interested in assuming the monastic habit outside the empire. The Russian authorities sought to control and regulate such tonsures by establishing procedures for checking their validity, and by ruling out automatic recognition of them in the empire. Individuals who were tonsured as monks abroad manipulated or tried to manipulate such regulations in order to facilitate travel back and forth from the Russian Empire for their own purposes. The result was that the real and apparent ambiguities that such rules allowed for were exploited by both state authorities and by real or fake monks themselves. The essay seeks to offer some perspectives on this phenomenon by focusing on four cases preserved in archival records. © 2023 Ltd "Integration: Education and Science". All rights reserved.
Keywords: Mount Athos; St. Panteleimon Monastery; dept.his; fake monks; monasticism; peer-reviewed; tonsures abroad

Sabbatical leave report: Fall 2013 - Nakamura, Byron (Distribution: Fall 2013 ; History., 2013)
This leave was devoted to research and revision of two conference papers submitted for publication, and to revision of a book chapter on boxing in the antiquity The chapter was submitted and accepted for publication in the Cambridge Companion to Boxing series.
Keywords: dept.his; faculty_collection; sabbatical_report

The Lion and the Lily: Map and Atlas Production in Early Modern England and France. - Petto, Christine Marie (2011)
Dr. Petto completed chapters 2 and 3 and a book proposal for her second manuscript, The lion and the lily: map and atlas production in early modern England and France. Chapter 2 describes local mapping and hydrographic charting initiatives in the 17th and 18th century; chapter 3 focuses on scientific cartography and the efforts of both crowns to map colonial interests in the Americas and Asia. She obtained book contract with Lexington Books, with release date of July 2013.
Keywords: dept.his; faculty_collection; sabbatical_report

Friday Night Fighter: "Indio" Ortega and the Golden Age of Televised Boxing. - Rondinone, Troy (Spring ; History., 2011)
Keywords: dept.his; faculty_collection; sabbatical_report

A History of Smallpox and Preventive Treatments for It in the Lands Bordering the South China Sea - Thompson, C. Michele (2011)
Keywords: dept.his; faculty_collection; sabbatical_report

Waging Wars of Quiet Survival: History of the Native Peoples of Connecticut. - Amerman, Stephen Kent (2010)
Keywords: dept.his; faculty_collection; sabbatical_report

War, Medicine and American Women in the Near East. - Metaxas, Virginia (2010)
Keywords: dept.his; faculty_collection; sabbatical_report

Womanpower in the 1960's, Fabian Feminism. - Beals, Polly (2009)
Worked on book about Fabian feminism. Finished the final chapter but book isn't complete yet. Wrote and delivered paper in London in March 2009. Is expanding book to include 1980's and 1990's Fabian feminism.
Keywords: dept.his; faculty_collection; sabbatical_report

Eighteenth-Century Russia. - Chrissidis, Nikolaos (2008)
Worked on a book and wrote and presented several paper on eighteenth century Russia.
Keywords: dept.his; faculty_collection; sabbatical_report

American Social Credit Movement. - Kalk, Bruce H. (2006)
Keywords: dept.his; faculty_collection; sabbatical_report

When France was King of 'Kartographie' - Petto, Christine Marie (2005)
Keywords: dept.his; faculty_collection; sabbatical_report

Amr al-Awzai Research. - Judd, Steven (2004)
Keywords: dept.his; faculty_collection; sabbatical_report

Northern Treasures and Southern Essences, an Exploration of Vietnamese Traditional Medicine. - Thompson, C. Michele (2004)
Keywords: dept.his; faculty_collection; sabbatical_report

Race and the Land in South Africa: African Challenges to Land Policy and Segregation Between 1905 and 1936. - Feinberg, Harvey M. (1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Biography of Connecticut Governor Ella T. Grasso] - Purmont, Jon E. (Fall;History., 1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Doctoral Dissertation Revision] - Kalk, Bruce H. (Fall;History., 1998)
Keywords: dept.his; faculty_collection; sabbatical_report

To Cope with a Bad Global Image: Human Rights in the People's Republic of China,1993-1994. - Lee, Ta-ling (Fall;History., 1996)
Keywords: dept.his; faculty_collection; sabbatical_report

History of the American Women's Hospitals in the early 20th century. - Quiroga, Virginia Anne Metaxas (1996)
Keywords: dept.his; faculty_collection; sabbatical_report

Land ownership, African agriculture and politics in South Africa, 1913-1939. - Feinberg, Harvey M. (1992)
Keywords: dept.his; faculty_collection; sabbatical_report

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Delicieux, 3 September - 8 December 1319. - Friedlander, Alan (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

Book Research and Testimony Before the House Subcommittee on International Law and Immigration and Refugees, October 2, 1991. - Hamilton-Merritt, Jane (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

A Biography of Ferdinand and Isabella. - Stewart, Paul (1989)
Keywords: dept.his; faculty_collection; sabbatical_report

Leonard Bacon. - Davis, Hugh (1988)
Keywords: dept.his; faculty_collection; sabbatical_report

Failure of Democracy: Human Rights in the People's Republic of China. - Lee, Ta-ling (Spring; History., 1988)
Keywords: dept.his; faculty_collection; sabbatical_report

The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. By HANNAH-LENA HAGEMANN. Edinburgh: EDINBURGH UNIVERSITY PRESS, 2021. Pp. xii + 316. $110, £85 - Judd, Steven C. (Journal of the American Oriental Society, 2023)
Keywords: book.review; dept.his

A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Monasteries - Hamilton-Merritt, Jane (Souvenir Press, 1976)
Keywords: Buddhism; Buddhist meditations; Hamilton-Merritt, Jane; Meditation; dept.his; faculty_collection

A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Temples - Hamilton-Merritt, Jane (Harper & Row, 1976)
Keywords: Buddhism; Hamilton-Merritt, Jane; Meditation; dept.his; faculty_collection

American Pacific Ocean Trade; Its Impact on Foreign Policy and Continental Expansion, 1784-1860 - Caruthers, J. Wade (Exposition-university book, 1973)
Keywords: Commerce; History; History; Pacific Area; History; United States; Pacific Area; United States; dept.his; faculty_collection

Walter Reuther, - Tyler, Robert L. (Great men of Michigan, 1973)
Keywords: Reuther, Walter, 1907-1970; dept.his; faculty_collection

The History of Kenya Agriculture. - Cone, L. Winston; Lipscomb, J. F. (University Press of Africa, 1972)
Keywords: Agriculture; History; Kenya; dept.his; faculty_collection

The Revenge of Heaven; Journal of a Young Chinese. - Ling, Ken; London, Miriam; Lee, Ta-ling (Putnam, 1972)
Keywords: 1949-; China; Politics and government; dept.his; faculty_collection

American Nativism, 1830-1860 - Leonard, Ira M.; Parmet, Robert D. (Anvil original, 1971)
Keywords: 1815-1861; Nativism; Immigrants; Politics and government; United States; United States; dept.his; faculty_collection

The Regulators in North Carolina: A Documentary History, 1759-1776. - Powell, William S.; Huhta, James K.; Farnham, Thomas J. (State Dept. of Archives and History, 1971)
Keywords: History; North Carolina; Regulator Insurrection, 1766-1771; Sources; dept.his; faculty_collection

Africana: Holdings of Books and Other African Resource Material in the Hilton C. Buley Library at Southern Connecticut State College - Southern Connecticut State College Library (Hilton C. Buley Library, Southern Connecticut State College, 1971)
Keywords: Africa; Bibliography; Catalogs; Africa; Connecticut; Library resources; New Haven; dept.his; faculty_collection

Gouverneur Morris and the American Revolution, - Mintz, Max M. (University of Oklahoma Press, 1970)
Report for Bachelor of Engineering (Naval Architecture)., ***CD-ROM held at loans desk***
Keywords: 1775-1783; New York (State); 1775-1783; United States; Biography; Legislators; Biography; United States; Foreign relations; History; Morris, Gouverneur, 1752-1816; Statesmen; Politics and government; Revolution, 1775-1783; dept.his; faculty_collection

Lyautey in Morocco: Protectorate Administration, 1912-1925 - Scham, Alan (University of California Press, 1970)
Keywords: Lyautey, Louis Hubert Gonzalve, 1854-1934; Morocco; Politics and government; dept.his; faculty_collection

Rebels of the Woods; the I.W.W. in the Pacific Northwest, - Tyler, Robert L. (University of Oregon Books, 1967)
Keywords: Industrial Workers of the World; dept.his; faculty_collection

Kenya Women Look Ahead - Oloo, Celina Nyai; Cone, Virginia S. (East African Literature Bureau, 1965)
Keywords: Kenya; Kenya; Social life and customs; Women; dept.his; faculty_collection

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge studies in modern history, 2020)
Keywords: Causes; Historiography; Historiography; World War, 1914-1918; World War, 1914-1918; dept.his; faculty_collection

The Saints of Progress: A History of Coffee, Migration, and Costa Rican National Identity - Kordick, Carmen (The University of Alabama Press, 2019)
"This work narrates the development of a historically remote--although internationally celebrated--coffee-growing region from the early 19th century through to the first decade of the 21st century. It considers the nation-building process from the margins to question traditional scholarly works that have reproduced, rather than deconstructed, Costa Rica's exceptionalist national mythologies that imagine this isthmian republic as Central America's 'white,' democratic, nonviolent, and egalitarian republic. The book recognizes that even though Costa Rica's exceptionalist rendition draws on some undeniable realities, it thoughtfully considers the origins, applicability, and longevity of the different elements of this exceptionalist master narrative. In particular, it suggests the mythology emerged during the Cold War, as revolution, civil war, military dictatorship, and state violence plagued much of Central America. In this same period, Costa Rica not only retained a relatively stable democratic system, but policymakers eliminated the standing army in 1948. This widely embraced and celebrated historical narrative, however, distorts as much as it illuminates the experience of contemporary and historical actors"--
Keywords: Coffee industry; Costa Rica; Costa Rica; History; Political aspects; dept.his

Sabbatical report on Contesting the Origins of the First World War - Paddock, Troy R. E. (2019)
Dr. Paddock spent the year completing a book and revising an article.
Keywords: dept.his; faculty_collection; sabbatical_report

Nightmare Factories The Asylum in the American Imagination - Rondinone, Troy (Johns Hopkins University Press, 2019)
Keywords: History; History; Asylums; Psychiatric hospitals; United States; dept.his; faculty_collection

To Master the Boundless Sea: The U.s. Navy, the Marine Environment, and the Cartography of Empire - Smith, Jason W. (Flows, migrations, and exchanges, 2018)
"As the United States grew into an empire in the late nineteenth century, notions like 'sea power' derived not only from fleets, bases, and decisive battles, but also from a scientific effort to understand and master the ocean environment. Beginning in the early nineteenth century and concluding in the first years of the twentieth, Jason W. Smith tells the story of the rise of the U.S. Navy and the emergence of American ocean empire through its struggle to control nature. In vividly told sketches of exploration, naval officers, war, and, most significantly, the ocean environment, Smith draws together insights from environmental, maritime, military, and naval history, and the history of science and cartography, placing the U.S. Navy's scientific efforts within a broader cultural context"--
Keywords: History, Naval; History; Cartography; Imperialism and science; United States; History; Nautical charts; SCSU Faculty Scholar Award; United States; United States. Navy; award_winner; dept.his; faculty_collection

Human Rights in the People's Republic of China - Wu, Yuan-li; Chang, Maria Hsia; Cooper, John F.; Gregor, A. James; Michael, Franz H.; Lee, Ta-ling (Westview special studies on China and East Asia, 2018)
Keywords: 20th century; Human rights; 21st century; China; History; Human rights; dept.his; faculty_collection

New Perspectives on Ibn ʻAsākir in Islamic Historiography - Judd, Steven C.; Scheiner, Jens J. (Islamic history and civilization ; v. 145, 2017)
This volume contains six articles on Ibn 'Asākir and his 'Ta'rīkh madīnat Dimāshq' illustrating a variety of perspectives and approaches to the material. It includes a seventh article that discusses the process by which the now standard 'Dār al-fikr' edition was compiled. The contributions address both the geographical and biographical sections of the 'Ta'rīkh madīnat Dimashq'. Some of the authors examine Ibn 'Asākir's sources, while others describe how Ibn 'Asākir's works were used by later generations of scholars and how he influenced multiple genres of later writings. The volume also contains analyses of individual biographies and discussions of Ibn 'Asākir's treatment of larger classes of people, including the first analysis of his biographies of women. In sum, it illustrates both the wide range of topics that the 'Ta'rīkh madīnat Dimashq' covers and the latest techniques for analyzing Ibn 'Asākir and his work.
Keywords: Historiography; Ibn ʻAsākir, ʻAlī ibn al-Ḥasan, 1105-1176. Tārīkh madīnat Dimashq; Islamic Empire; dept.his; faculty_collection

This City Belongs to You: A History of Student Activism in Guatemala, 1944-1996 - Vrana, Heather A. (University of California Press, 2017)
"Between 1944 and 1996, Guatemala experienced a revolution, counterrevolution, and civil war. In the middle of these national shifts were students from Guatemala's only public university, the University of San Carlos (USAC). USAC students served in, advised, protested, and were later persecuted by the government, all the while crafting a powerful student nationalism founded on their responsibility to lead the nation. In no other moment has the relationship between the university and the state been so mutable, yet so mutually formative. By showing how the very notion of the middle class in Guatemala emerged from these student movements, this book places an often-marginalized region and period at the center of histories of class, protest, and youth movements, while providing an entirely new way to think about the role of universities and student bodies in the formation of liberal democracy throughout Latin America.
Keywords: 20th century; Guatemala; History; Student movements; dept.his; faculty_collection

An Academy at the Court of the Tsars: Greek Scholars and Jesuit Education in Early Modern Russia - Chrissidis, Nikolaos A. (NIU Press, 2015)
Keywords: 17th century; 17th century; Education, Higher; 17th century; Greeks; Education; History; History; Jesuits; Leichoudēs, Iōannikios, 1633-1717; Leichoudēs, Sōphronios, 1652-1730; Moskovskai︠a︡ slavi︠a︡no-greko-latinskai︠a︡ akademii︠a︡; Moscow; Russia; Russia (Federation); dept.his; faculty_collection

Our Land, Our Life, Our Future: Black South African Challenges to Territorial Segregation, 1913-1948 - Feinberg, Harvey M. (Hidden histories series, 2015)
Keywords: 1909-1961; History; History; South Africa; Land reform; Law and legislation; South Africa; dept.his; faculty_collection

Major Problems in American Indian History: Documents and Essays - Hurtado, Albert L.; Iverson, Peter; Bauer, William J.; Amerman, Stephen Kent (Major problems in American history series, 2015)
Keywords: History; History; Indians of North America; Indians of North America; Sources; dept.his; faculty_collection

Mapping and Charting in Early Modern England and France: Power, Patronage, and Production - Petto, Christine Marie (Toposophia, 2015)
Keywords: Cartography; England; France; History; History; Cartography; History; Map industry and trade; Paris; dept.his; faculty_collection

Vietnamese Traditional Medicine: A Social History - Thompson, Claudia Michele (History of medicine in Southeast Asia series, 2015)
Keywords: History; Medicine, Chinese; History; Vietnam; Medicine, Traditional; SCSU Faculty Scholar Award; Vietnam; award_winner; dept.his; faculty_collection; history; Medicine, Chinese Traditional; history; Smallpox; prevention & control; Traditional medicine

World War I and Propaganda - Paddock, Troy R. E. (History of warfare ; v. 94, 2014)
Keywords: Propaganda; World War, 1914-1918; dept.his; faculty_collection

Dr. Ruth A. Parmelee and the Changing Roll of Near East Missionaries in Early Twentieth Century Turkey - Metaxas, Virginia (Role of the American Board in the World: Bicentennial Reflections on the Organization's Missionary Work, 1810-2010, 2012)
The American Board of Commissioners for Foreign Missions (ABCFM) was the country's first creator of overseas Christian missions. Founded in 1810 and supported by a coalition of Calvinist denominations, the ABCFM established the first American missions in India, China, Africa, Oceania, the Middle East, and many other places. It was America's largest missionary organization in the nineteenth century, and its influence was immense. Its missionaries established the first Western schools and hospitals in many parts of the world, and they successfully promoted women's rights and other ideals from the Enlightenment. They also transformed oral languages such as Zulu, Hawaiian, and Cherokee into written form, and they preserved many elements of premodern cultures (albeit not always intentionally). The contributors to this book provide valuable insights on the work of the ABCFM (which exists today under a different name). Some of the contributors profile the lives of notable ABCFM missionaries, others focus on ideological shifts within the Board, and still others chronicle the Board's role in historic events, including the Opium Wars, the colonization of Hawai'i, and the Armenian Genocide. From reading this book, people will come to understand why the ABCFM is widely viewed as America's most historically significant missionary organization.
Keywords: American Board of Commissioners for Foreign Missions; History; Congregational churches; Missions; Missions, American; dept.his; faculty_collection

Southern Medicine for Southern People Vietnamese Medicine in the Making - Monnais-Rousselot, Laurence; Thompson, Claudia Michele; Wahlberg, Ayo (Cambridge Scholars Pub., Cambridge Scholars Publishing, 2012)
What is a national medicine? What does it mean for a medicine to be traditional and scientific at the same time? How could a specifically Vietnamese medicine emerge out of the medical practices and treatments that have flourished and waned during key soci
Keywords: History; Traditional medicine; Vietnam; Vietnam; Traditional medicine; dept.his; faculty_collection

Religion and Identity in Russia and the Soviet Union A Festschrift for Paul Bushkovitch - Chrissidis, Nikolaos A. (Slavica Publishers, Slavica, 2011)
Keywords: Bushkovitch, Paul; Nationalism; History; Christianity and politics; History; Identity (Psychology); History; Nationalism; History; Soviet Union; Politics and government; Politics and government; Russia; Religious aspects; Russia; Russkai͡a pravoslavnai͡a t͡serkovʹ; National characteristics, Russian; Soviet Union; dept.his; faculty_collection

We Will Be Satisfied with Nothing Less: The African American Struggle for Equal Rights in the North During Reconstruction - Davis, Hugh (Cornell University Press, 2011)
Historians have focused almost entirely on the attempt by southern African Americans to attain equal rights during Reconstruction. However, the northern states also witnessed a significant period of struggle during these years. Northern blacks vigorously protested laws establishing inequality in education, public accommodations, and political life and challenged the Republican Party to live up to its stated ideals. In "We Will Be Satisfied With Nothing Less," Hugh Davis concentrates on the two issues that African Americans in the North considered most essential: black male suffrage rights and equal access to the public schools. Davis connects the local and the national; he joins the specifics of campaigns in places such as Cincinnati, Detroit, and San Francisco with the work of the National Equal Rights League and its successor, the National Executive Committee of Colored Persons. The narrative moves forward from their launching of the equal rights movement in 1864 to the "end" of Reconstruction in the North two decades later. The struggle to gain male suffrage rights was the centerpiece of the movement's agenda in the 1860s, while the school issue remained a major objective throughout the period. Following the ratification of the Fifteenth Amendment in 1870, northern blacks devoted considerable attention to assessing their place within the Republican Party and determining how they could most effectively employ the franchise to protect the rights of all citizens.-- Book jacket.
Keywords: 1863-1877; African Americans; 19th century; Equality before the law; 19th century; Reconstruction (U.S. history, 1865-1877); African Americans; Civil rights; History; United States; dept.his; faculty_collection

Urban Indians in Phoenix schools, 1940-2000 - Amerman, Stephen Kent (Indigenous education, 2010)
"In the latter half of the twentieth century, tens of thousands of Native American families moved to cities across the United States, some via the government relocation program and some on their own. In the cities, they encountered new forms of work, entertainment, housing, and education. In this study, Stephen Kent Amerman focuses on the educational experiences of Native students in urban schools in Phoenix, Arizona, a city with one of the largest urban Indian communities in the nation. The educational experiences of Native students in Phoenix varied over time and even in different parts of the city, but interactions with other ethnic groups and the experience of being a minority for the first time presented distinctive challenges and opportunities for Native students., Using oral histories as well as written records, Amerman examines how the Phoenix schools tried to educate and assimilate the Native students alongside Hispanic, Asian, black, and white students and how Native children, their parents, and the Indian community at large responded to this new urban education and the question of their cultural identity. Reconciling these pressures was a struggle, but many found resourceful responses, charting paths that enabled them to acquire an urban education while still remaining Indian."--Pub. desc.
Keywords: 20th century; 20th century; Education; 20th century; Indians of North America; 20th century; Public schools; 20th century; Urban schools; 20th century; Urbanization; Arizona; Cultural assimilation; Education; History; Indians of North America; Phoenix; Social aspects; award_winner; dept.his; faculty_collection

The Great Industrial War Framing Class Conflict in the Media, 1865-1950 - Rondinone, Troy (Rutgers University Press, 2010)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers. Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported.
Keywords: History; History; Social conflict; Labor disputes; United States; dept.his; faculty_collection

The System: The American Constitution in Historical Perspective 1763-1929 - Gerber, Richard A. (Cengage Learning, 2009)
Keywords: United States; United States. Constitution; Constitutional history; dept.his; faculty_collection

Revolution and Union: The American Dilemma 1763-1877 - Gerber, Richard A. (Cengage Learning, 2008)
Keywords: History; Textbooks; United States; dept.his; faculty_collection

The Civil Rights Act of 1875: A Reexamination - Gerber, Richard A.; Friedlander, Alan (Transactions of the Connecticut Academy of Arts and Sciences ; v. 60, p. 1-150, 2008)
Keywords: Civil rights; History; History; African Americans; United States; dept.his; faculty_collection

Not Your (founding) Fathers' Constitution: Teaching United States Constitutional History - Gerber, Richard A. (The Connecticut Urban Consortium ; New Haven Public Schools, 2007)
Synopsis of the lectures presented during the three-year program, together with a PowerPoint presentations on CD-ROM. This material can be used for preparation of classroom instructional program or directly in the classroom.
Keywords: History; Study and teaching; Study and teaching; Constitutional history; United States. Constitution; United States; United States; dept.his; faculty_collection

When France Was King of Cartography: The Patronage and Production of Maps in Early Modern France - Petto, Christine Marie (Toposophia, 2007)
When France Was King of Cartography investigates over a thousand maps and nearly two dozen map producers, analyzes the map as a cultural artifact, map producers as a group, and the array of map viewers over the course of two centuries in France. The book focuses on situated knowledge or 'localized' interests reflected in these geographical productions. Through the lens of mapmaking, it examines the relationship between power and the practice of patronage, geography, and commerce in early modern France.
Keywords: 17th century; Cartography; 17th century; Map industry and trade; 18th century; 18th century; Map industry and trade; Cartography; France; History; SCSU Faculty Scholar Award; award_winner; dept.his

Crisis of the Black Intellectual - Wright, W. D. (Third World Press, 2007)
Keywords: African American intellectuals; African Americans; Intellectual life; dept.his; faculty_collection

Black History and Black Identity: A Call for a New Historiography - Wright, W. D. (Praeger, 2002)
Keywords: African Americans; Historiography; African Americans; Race identity; dept.his; faculty_collection

The Origins of the Southern Strategy: Two-Party Competition in South Carolina, 1950-1972 - Kalk, Bruce H. (Studies in modern American history, 2001)
Keywords: 1951-; 20th century; South Carolina; History; Political parties; Politics and government; South Carolina; dept.his; faculty_collection

The Hammer of the Inquisitors: Brother Bernard Délicieux and the Struggle Against the Inquisition in Fourteenth-Century France - Friedlander, Alan (Cultures, beliefs, and traditions ; v. 9, 2000)
Keywords: Bernard, Délicieux, frère, approximately 1260-approximately 1320; Franciscans; Biography; Inquisition; Church history; France; Languedoc; Languedoc; Languedoc (France); dept.his; faculty_collection

Seeds of Empire: The American Revolutionary Conquest of the Iroquois - Mintz, Max M. (World of war, 1999)
"The American Revolution was a struggle not only for independence, but for the lands of Native Americans. The jewel in this conflict was the upstate New York domain of the Iroquois Six Nations, where fertile river valleys were a magnet for farmers weary of New England's stubborn soil." "While at first intentionally neutral, the Iroquois were soon forced to choose sides between either rebel or British forces. Seeds of Empire recreates the events surrounding General John Sullivan's scorched-earth campaign against the Six Nations of the American Indians of New York and the Eastern territories in 1779, following the surrender of General John Burgoyne's entire British army at the Battle of Saratoga. Abandoned by both the rebels and the British at the end of the revolution and devastated by the ravages of war, the Iroquois found themselves powerless to resist the post-Revolutionary takeover and peopling of their heartland by the new American nation."--Jacket.
Keywords: Sullivan's Indian Campaign, 1779; dept.his; faculty_collection

Leonard Bacon: New England Reformer and Antislavery Moderate - Davis, Hugh (Louisiana State University Press, 1998)
A nationally powerful reformer, editor, church leader, and author, Leonard Bacon (1802-1881) influenced the thinking of northern Protestants for more than fifty years. In this detailed biography, Hugh Davis offers the first scholarly treatment of Bacon's life and work. Convinced that he was obligated to educate the American people on a broad range of social, political, and theological issues, Bacon, a Congregational minister, actively sought to connect his church and community to the larger world of organized benevolence, religious and reform journalism, social activism, and scholarship. The son of New England Congregational missionaries to the native Americans on the Michigan frontier, he also endeavored to extend evangelical religion and New England ideas and institutions to the rest of the nation and even overseas. Offering new insights into the nineteenth-century Protestant ministry, the evangelical mentality, and the efforts of Americans in Bacon's generation to address the moral and social issues of their time, Leonard Bacon will prove an invaluable contribution to American religious, social, and political history.--(Source of description unspecified.)
Keywords: Bacon, Leonard, 1802-1881; Congregational churches; Biography; Clergy; United States; award_winner; dept.his; faculty_collection

Racism Matters - Wright, W. D. (Praeger, 1998)
This work offers a discussion of racism in America focusing on how white people have been affected by their own racism and how it impacts upon relations between blacks and whites. It draws attention to how racism is different from race and shows how whites have maintained a white racist America.
Keywords: Race relations; Racism; United States; United States; dept.his; faculty_collection

A Concise History of the United States with Documents - House, Lewis; Purmont, Jon E.; Leonard, Ira M. (TLI Press, 1997)
Keywords: History; United States; dept.his; faculty_collection

Black Intellectuals, Black Cognition, and a Black Aesthetic - Wright, W. D. (Praeger, 1997)
Keywords: African American intellectuals; African Americans; Intellectual life; African American aesthetics; African Americans; Race identity; dept.his; faculty_collection

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Délicieux, 3 September-8 December 1319 - Friedlander, Alan (Transactions of the American Philosophical Society ; v. 86, pt. 1, 1996)
Keywords: Bernard, Délicieux, frère, approximately 1260-approximately 1320; Trials, litigation, etc; dept.his; faculty_collection

Portrait of an Unknown Man: Manuel Azaña and Modern Spain - Rivas Cherif, Cipriano de; Stewart, Paul; Rivas, Enrique de (Fairleigh Dickinson University Press ; Associated University Presses, 1995)
Keywords: 1931-1939; Azaña, Manuel, 1880-1940; Presidents; Biography; Spain; Politics and government; Spain; dept.his; faculty_collection

A Concise History of the United States. - House, Lewis; Purmont, Jon E.; Leonard, Ira (TLI Press, 1994)
Keywords: History; United States; dept.his; faculty_collection

The Bamboo Gulag: Human Rights in the People's Republic of China, 1991-1992 - Lee, Ta-ling; Copper, John Franklin (Occasional papers/reprints series in contemporary Asian studies, 1994)
Keywords: 1976-2002; China; China; China; Civil rights; Human rights; Politics and government; dept.his; faculty_collection

Tragic Mountains: The Hmong, the Americans, and the Secret Wars for Laos, 1942-1992 - Hamilton-Merritt, Jane (Indiana University Press, 1993)
Keywords: 20th century; 20th century; Laos; Government policy; History; Hmong (Asian people); Laos; Hmong (Asian people); Politics and government; Laos; Wars; Hmong (Asian people); dept.his; faculty_collection

Failure of Democracy Movement: Human Rights in the People's Republic of China, 1988/89 - Lee, Ta-ling; Copper, John Franklin (Occasional papers/reprints series in contemporary Asian studies ; no. 103, 1991)
Keywords: China; China; China; Civil rights; History; Human rights; Tiananmen Square Incident, 1989; dept.his; faculty_collection

Joshua Leavitt, Evangelical Abolitionist - Davis, Hugh (Louisiana State University Press, 1990)
Keywords: 1815-1861; United States; 19th century; United States; Biography; Antislavery movements; History; Leavitt, Joshua, 1794-1873; Abolitionists; Social conditions; To 1865; United States; United States; Evangelicalism; dept.his; faculty_collection

The Generals of Saratoga: John Burgoyne and Horatio Gates - Mintz, Max M. (Yale University Press, 1990)
Keywords: Burgoyne, John, 1722-1792; Gates, Horatio, 1728-1806; Saratoga Campaign, N.Y., 1777; dept.his; faculty_collection

One Step Forward, One Step Back: Human Rights in the People's Republic of China in 1987/88 - Copper, John Franklin (Occasional papers/reprints series in contemporary Asian studies, 1989)
Keywords: 1976-2002; China; China; Human rights; Politics and government; dept.his; faculty_collection

Africans and Europeans in West Africa: Elminans and Dutchmen on the Gold Coast During the Eighteenth Century - Feinberg, Harvey M. (Transactions of the American Philosophical Society ; v. 79, pt. 7, 1989)
Keywords: Dutch; Ghana; Elmina (Ghana); History; award_winner; dept.his; faculty_collection

Fairfield: The Biography of a Community, 1639-1989 - Farnham, Thomas J. (Published for the Fairfield Historical Society by Phoenix Pub., 1988)
Keywords: Fairfield (Conn.); History; dept.his; faculty_collection

Student Protests in Connecticut Colleges and Universities, 1701-1870: Yale College as a Case Study - Purmont, Jon Emmett (Thesis Ph. D.--Columbia University., 1988)
Keywords: Case studies; Education, Higher; Connecticut; History; History; Students; Political activity; Yale University; dept.his; faculty_collection

Reform in Reverse: Human Rights in the People's Republic of China, 1986/1987 - Lee, Ta-ling; Copper, John Franklin (Occasional papers/reprints series in contemporary Asian studies ; no. 1987-6 (83), 1987)
Keywords: China; Human rights; dept.his; faculty_collection

Manifest Destinies: The Usa, the Ussr - Mintz, Max M.; Bennet, John (Imperial visions, 1987)
Keywords: History; History; Russia; History; Soviet Union; United States; dept.his; faculty_collection

Upper State Street 1640-1982 - Farnham, Thomas J. (s.n., 1983)
Keywords: New Haven (Conn.); Streets; Upper State Street; dept.his; faculty_collection

Vigil in Benicarló - Azaña, Manuel (Fairleigh Dickinson University Press, 1982)
Keywords: Civil War, 1936-1939; Drama; History; Spain; dept.his; faculty_collection

Hmong and Yao: Mountain Peoples of Southeast Asia - Hamilton-Merritt, Jane (SURVIVE, 1982)
Keywords: Hmong (Asian people); Yao (Southeast Asian people); Chemical warfare; award_winner; dept.his; faculty_collection

My First Days of School - Hamilton-Merritt, Jane (Simon & Schuster, 1982)
Five-year-old Kate relates the experiences of her first day in kindergarten.
Keywords: dept.his; faculty_collection

Our New Baby - Hamilton-Merritt, Jane (J. Messner, 1982)
Follows the experiences and changing feelings of a child during a year when a new baby becomes a part of his family.
Keywords: Infants; Juvenile literature; Juvenile literature; Parent and child; Juvenile literature; Siblings; dept.his; faculty_collection

Superpowers, the USA, the USSR - Mintz, Max M.; Bennet, John (Imperial visions, 1980)
Keywords: History; History; Soviet Union; United States; dept.his; faculty_collection

Weston: The Forging of a Connecticut Town - Farnham, Thomas J. (Published for the Weston Historical Society by Phoenix Pub., 1979)
Keywords: History; Weston (Conn.); dept.his; faculty_collection

Historians and Slavery: A Critical Analysis of Perspectives and Irony in American Slavery, and Other Recent Works. - Wright, W. D. (1978)
Keywords: Genovese, Eugene D., 1930-2012; Engerman, Stanley L; Perspectives and irony in American slavery; Slavery; Historiography; United States; dept.his; faculty_collection

Urban legacy: the story of America's cities - Klebanow, Diana (Mentor book ; ME1586, 1977)
Keywords: Cities and towns; History; United States; dept.his; faculty_collection

Western Science in Indochina, 1800-1998 - Thompson, C Michele (The Cambridge History of Science Vol. 8, Modern Science in National and International Context, 2020)
Keywords: dept.his

A Narrative That Was Not Her Own: Mary I as Mediterranean Queen - Kern, Darcy (Writing Mary I: History, Historiography, and Fiction, 2022)
Nearly every biography of Mary Tudor mentions her acquisition of the Kingdom of Naples and the Spanish kingdoms through her marriage to Philip Habsburg, later Philip II of Spain, but they say little about her role as queen consort, primarily because she failed to control the narrative of her reign. She made little effort to patronize writers, disperse her symbols, send images of herself, use masculine terminology like her grandmother Isabel of Castile, or involve herself in the governance of her Mediterranean kingdoms. Her real and symbolic absence in the south, and the presence of Doña Juana, Philip’s sister and the capable regent of the Spanish kingdoms in his absence, led to her marginalization. This has had long-lasting consequences for the historiography of her reign, as historians have generally confined themselves to studying her in her English context using the gendered language of early Spanish writers while omitting her entirely from Naples.
Keywords: award_winner; dept.his

The nature of geography and the Schaefer-Hartshorne debate - Martin, G.J. (Reflections on Richard Hartshorne's "The nature of geography', 1989)
The tendency by geographers to cast Hartshorne as either hero or villain in modern American geography is clearly represented in this essay considering the Hartshorne-Schaefer controversy, a dispute of almost mythical proportions in the modern history of American geography. Through analysis of unpublished and published documents, the author provides us with a wealth of historical information concerning the relation between the two antagonists and the events surrounding the publication of their methodological statements. The reportage has an additional, illocutionary impact that derives from the introduction of historical specificities into the discussion of mythologized events. The description and evaluation of the events surrounding this episode in American geography, especially its portrayal of spatial analysts in the uncharacteristic role of loyal sentimentalists, will probably add fuel to the dying embers of this controversy. -from Editors
Keywords: American geography; Hartshorne; R.; Schaefer; dept.egm; geographers; historical information; illocutionary impact; methodological statement; spatial analysts; ⛔ No DOI found

Access to archives and privacy: The twenty-third international archival round table conference proceedings - Newhall, A.C. (American Archivist, 1989)
Keywords: dept.his

Competitive hagiography in biographies of al-Awzā'ī and Sufyān al-Thawrī - Judd, S.C. (Journal of the American Oriental Society, 2002)
The present paper examines how followers of 'Abd al-Rahcombining dot belowmān b. 'Amr al-Awzā'ī and Sufyān al-Thawrī tried to create boundaries between the nascent madhhabs that claimed them as eponyms. In the absence of significant differences in legal method, students turned to the two shaykhs' responses to the 'Abbāsid revolution to draw distinctions between them. The Arabic biographical sources contain stories of their responses to the revolution that reveal a dialogue between followers of the two shaykhs about the relative merits of their choices. The changing interpretations of their attitudes toward the 'Abbāsid regime and the exaggeration evident in the anecdotes examined have significant implications for our reading of medieval Arabic biographical sources.
Keywords: dept.his

From l'état, c'est moi to l'état, c'est l'état: Mapping in early modern France - Petto, C.M. (Cartographica, 2005)
Using the printed works of two French cartographers, Alexis-Hubert Jaillot and Guillaume Delisle, I investigate how the changing interests of the government directed not only the process of map-making but the rhetoric evident in printed maps and atlases. Jaillot, a commercial map publisher flourishing during the second half of the seventeenth century, produced maps that participated in the fabrication of the image of Louis XIV. Maps served this "cult of image" and contributed to a multimedia show to glorify the reign of the Sun King and to support his personal state - l'état, c'est moi. In the eighteenth century, while a rhetoric of image was still present on printed maps, the "cult of image" was dead and mapping appealed to the rise of the impersonal or bureaucratized state - l'état, c'est l'état. Delisle produced maps as instruments of statecraft that aided the state in furthering its domestic and international interests. In particular, printed maps of the Americas served the government's need to acquire greater territorial control. While images were still powerful on New World maps, the French boundary claims, egregious to some, if uncontested could be produced time and again as a true representation and legitimization of territorial control.
Keywords: Cartography; France; History; Image; Louis XIV; Printed maps; Rhetoric; Scientific authority; dept.his; eighteenth century; historical cartography; mapping method; territorial delimitation

In defense of homology and history: A response to Allen - Paddock, T. (Philosophy and Geography, 2004)
Keywords: dept.his

"I should not be wearing a pilgrim hat": Making an Indian place in urban schools, 1945-75 - Amerman, S. (American Indian Culture and Research Journal, 2007)
Keywords: dept.his

Playing the feminine card: Women of the early modern map trade - Petto, C.M. (Cartographica, 2009)
Images of allegorical women have often appeared on maps or in atlas frontispieces as objects in need of security provided by male protectors or as the counterpoint, objects to be dominated by male possessors. Exploring the role of women in the early modern map trade initially reveals not only a similar male dominance but also similar calls for protection. Nearly 10 years ago, Alice Hudson and Mary McMichael Ritzlin produced a checklist of about 300 pre-twentieth-century women in cartography. The present work contributes to the further investigation of some of these women in the early modern map trade and studies in the allied field of book printing, and more general works on women in commercial trade provide the framework for this piece. Women in the map trade were quite cognizant of the challenges of their gender and used a feminine discourse-that is, they played the feminine card-when it served their interests. All of these women, however, participated in the male discourse of the corporate community, which entailed not only making contracts and partnerships and advertising and producing new works but also making use of the social network within the trade, as well as exploiting the patronage connections cultivated by their husbands before them.
Keywords: Angleterre; England; France; commerce de l'impression des cartes; dept.his; engravers; femmes; graveurs; image; map publishers; map-printing trade; women; éditeurs cartographiques

The great industrial war: Framing class conflict in the media, 1865-1950 - Rondinone, T. (The Great Industrial War: Framing Class Confl ict in the Media, 1865-1950, 2009)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers.Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported. copyright © 2010 by Troy Rondinone All rights reserved.
Keywords: dept.his

Reconstructing meaning in Deuteronomy 22:5: Gender, society, and transvestitism in Israel and the ancient Near East - Vedeler, H.T. (Journal of Biblical Literature, 2008)
Keywords: dept.his

Sex, drink, and drugs: Tobacco in seventeenth-century Russia - Chrissidis, N.A. (Tobacco in Russian History and Culture: From the Seventeenth Century to the Present, 2011)
Keywords: dept.his

Manufacturing Mohism in the Mencius - Radice, T. (Asian Philosophy, 2011)
The Mencius contains several negative remarks about the Mohists and their doctrine of 'universal love' (jian'ai). However, little attention has been paid to whether Mencius' descriptions of Mohism were accurate. Fortunately, there is a surviving record of the beliefs of Mozi in the text that bears his name. In this essay, I analyze this text and descriptions of Mohism from other early Chinese texts, and compare them to the criticisms of Mohism in the Mencius. Ultimately, I show that the image of the Mohists as ones who promoted a doctrine that contradicted filial piety was inaccurate, and obscured the complexities of filial piety in the Warring States period. © 2011 Taylor and Francis.
Keywords: dept.his; peer-reviewed

Ella Grasso: Connecticut's pioneering governor - Purmont, J.E. (Ella Grasso: Connecticut's Pioneering Governor, 2012)
When Ella Tambussi Grasso ran for governor of Connecticut in 1974, she had not lost an election since she was first voted into the state's General Assembly in 1952. The people of Connecticut chose her as the nation's first woman to be elected governor in her own right-the capstone of a long and successful career dedicated to public service, effective government, and the democratic process. During her tenure as governor, Grasso's leadership was tested in the face of fiscal problems, state layoffs, and budget shortfalls. The daughter of Italian immigrants, she endeared herself to her constituents during the great Blizzard of 1978, when she stayed at the State Armory around the clock to direct emergency operations and make frequent television appearances. Author Jon E. Purmont, who served as Grasso's executive assistant when she was governor, draws on his diary from that time, research in Grasso's archives, and interviews with Grasso's family and friends to give us a rich and intimate portrait of this political pioneer. © 2012 Jon E. Purmont. All rights reserved.
Keywords: dept.his

Would a saola by any other name still be a saola?: Appropriating rare animals, expropriating minority peoples - Thompson, C.M. (State, Society and the Market in Contemporary Vietnam: Property, Power and Values, 2012)
Keywords: dept.his

Divergent paths: Processes of identity formation among German speakers, 1730-1760 - McDaniel, M.B. (A Peculiar Mixture: German-Language Cultures and Identities in Eighteenth-Century North America, 2013)
Keywords: dept.his

Friday Night Fighter: Gaspar "Indio" Ortega and the Golden Age of Television Boxing - Rondinone, Troy (University of Illinois Press, 2013)
Friday Night Fighter relives a lost moment in American postwar history, when boxing ruled as one of the nation's most widely televised sports. During the 1950s and 1960s, viewers tuned in weekly, sometimes even daily, to watch widely-recognized fighters engage in primordial battle, with the Gillette Cavalcade of Sports Friday Night Fights being the most popular fight show. Troy Rondinone follows the dual narratives of the Friday Night Fights show and the individual story of Gaspar "Indio" Ortega, a boxer who appeared on primetime network television more than almost any other boxer in history. From humble beginnings growing up poor in Tijuana, Mexico, Ortega personified the phenomenon of postwar boxing at its greatest, appearing before audiences of millions to battle the biggest names of the time, such as Carmen Basilio, Tony DeMarco, Chico Vejar, Benny "Kid" Paret, Emile Griffith, Kid Gavilan, Florentino Fernández, and Luis Manuel Rodriguez.--(Source of description unspecified.)
Keywords: Hispanic Americans; History; History; Boxing; History; Television broadcasting of sports; Ortega, Gaspar "Indio", 1935-; Boxing; United States; United States; Sports; dept.his; faculty_collection

Greeks in seventeenth-century Russia - Chrissidis, N.A. (Portraits of Old Russia: Imagined Lives of Ordinary People, 1300-1745, 2015)
Keywords: dept.his

Soul sister journey: Essence magazine and travel columns during the “me” decad - Carter-David, S. (Women's Magazines in Print and New Media, 2016)
Keywords: dept.his

Were the umayyad-era qadarites Kāfirs? - Judd, S. (Islam. Hist. Civiliz., 2016)
Keywords: dept.his

Platonic words: Paolo sarpi and roberto bellarmino as translators in the venetian interdict crisis - Kern, D. (Philological Quarterly, 2016)
Keywords: dept.his; ⛔ No DOI found

To know the distance: Wayfinding and roadmaps of early modern England and France - Petto, C.M. (Cartographica, 2016)
In 1675, John Ogilby produced his road atlas with strip maps which not only arrived with fanfare, but spawned several more publications that aimed to be user-friendly. As with many maps and atlases from the London printing trade, the objectives were to serve consumers, acquire a piece of the market, and have an outlet for a new edition. Across the Channel, however, the road network of France, as with other public works, was not only state-directed but a tool of state power. Not until nearly one hundred years later did Claude-Sidoine Michel and Louis-Charles Desnos produce L'Indicateur Fidele, which provided strip maps for merchants, navigators, and travelers. This publication emerged out of the French national mapping project directed by the Cassini family. In the interim, while French map makers produced maps with an appeal to serving the state, they, like their London contemporaries, also hoped to maintain a thriving business and attract an audience, often through the traditional French social institution of patronage. The purpose of this comparative study of (post) road maps and atlases of England and France is to investigate the role of the government and the publishing trade in the production of these works. © 2016 University of Toronto Press.
Keywords: Consumers; England; France; London [England]; Map trade; Patronage; Post roads; Strip maps; United Kingdom; cartography; dept.his; mapping

Thou uncracked keel: The many voyages of the Whaleship Charles W. Morgan and the presence of the American Maritime past - Smith, J.W. (New England Quarterly-A Historical Review of New England Life and Letters, 2016)
The ship wherein Theseus and the youth of Athens returned from Crete had thirty oars, and was preserved by the Athenians down even to the time of Demetrius Phalereus, for they took away the old planks as they decayed, putting in new and stronger timber in their place, in so much that this ship became a standing example among the philosophers, for the logical question of things that grow; one side holding that the ship remained the same, and the other contending that it was not the same. © 2016 by The New England Quarterly. All rights reserved.
Keywords: dept.his

The lands of orthodoxy in the seventeenth century circa 1590-1720 - Bushkovitch, P.; Chrissidis, N.A.; Pǎun, R.G. (Cahiers du Monde Russe, 2017)
Keywords: dept.his

Signum meum apposui: Notaries and their signs in medieval languedoc - Friedlander, A. (The Experience of Power in Medieval Europe, 950-1350, 2017)
Keywords: dept.his

To the editors - Forbes, R.P.; Mintz, S.; Stauffer, J. (American Historical Review, 2019)
Keywords: dept.his; ⛔ No DOI found

Intellectuals and “democratic elements”: A distrusted underclass - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
As the targets of numerous campaigns, intellectuals have sustained mental torment and physical suffering on a large scale. Like the deprivation of human rights for biological and genetic reasons in other lands or other ages, Chinese intellectuals were destined to suffer abridgement of their human rights in the People’s Republic of China for political and ideological reasons. The term “intellectuals” refers to all those who have had a middle school/higher education and those with similar educational levels. Included in the ranks of intellectuals were members of the so-called democratic parties. These people, never large in number, were mostly well educated and well known in intellectual circles. The Cultural Revolution will be long remembered by intellectuals not only as a period of continued mental torment from the earlier days, but more particularly as a period of the most cruel physical abuses in human history. Intellectuals, deprived of their most precious human rights, continue to exist in mainland China as an underclass. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Red guards and political dissidents (I): Tools of violence and power struggle - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
In 1966, Mao Zedong launched the Great Proletarian Cultural Revolution in a last attempt to remake China in his image. He believed that the country was led by a party infested from the top on down with “capitalist-roaders” who had betrayed the proletarian goals of true socialism by following the bourgeois line. Denied support in the power structure, Mao sought help from the outside, mobilizing millions of high school and college students as the “Red Guards” to strike down his enemy in an unprecedented campaign that left the nation nearly paralyzed. Red Guard organizations of confusing ideological persuasions soon proliferated throughout the country, and the whole movement quickly got out of control and degenerated into total chaos. That the Red Guards were used by Mao as a tool in the ideologically based power struggle within the party is not only the consensus of most observers but also has been freely admitted by many former Red Guards. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Red guards and political dissidents (II): Victims beyond a generation - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
Many former Red Guards who through the Cultural Revolution were encouraged to participate in unrestrained violence, saw the seamy side of the regime as a result and were themselves eventually suppressed and reached the conclusion that the system was corrupt and had to be changed. Former Red Guards who turned political activists varied greatly in their often vaguely defined outlooks and their intensity of commitment and activity. Wei Jingsheng, China’s most celebrated Red Guard-turned dissident, related a similar experience in an unfinished autobiographical account written before his arrest and smuggled out of the country in 1980. Many former Red Guards understandably see a silver lining in the destructive rampage they committed during the height of the Cultural Revolution. The Red Guard movement has come full circle. The human rights tragedy of the movement is threefold. In the first stage, the Red Guards were Mao’s “little generals” trampling on the human rights of their victims. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Prime (and crime) time: Boxing in the 1950s - Rondinone, T. (The Camb. Companion to Box., 2019)
Keywords: dept.his

Human rights in the people’s republic of China - Wu, Y.-L.; Michael, F.; Copper, J.F.; Lee, T.-L.; Chang, M.H.; Gregor, A.J. (Human Rights in the People's Republic of China, 2019)
This book examines the effects that political institutions, the legal system, and economic policies have had on the human rights record in the PRC since 1949. The authors first address the problems of assessing political liberties in a nation that emphasizes economic over civil rights and that has traditionally valued collective rights over individ. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

A dramaturgy of death: Performing (and spectating) filial piety in early china - Radice, T. (Journal of Chinese History, 2022)
This essay analyzes the early Chinese elite discourse on filial death rituals, arguing that early Chinese texts depict these rituals as performance events. Building on spectacle of xiao sacrifices in the Western Zhou Dynasty, Eastern Zhou authors conceived of filial death rituals as dramaturgical phenomena that underscored not only what needed to be performed, but also how it should be performed, and led to an important distinction between personal dispositions and inherited ritual protocol. This distinction, then, led to concerns about artifice in human behavior, both inside and outside the Ruist (Confucian) tradition. By end of the Warring States Period and in the early Western Han Dynasty, with the embracement of artifice in self-cultivation, the dramatic role of the filial son in death rituals became even more developed and complex, requiring the role of cultivated spectators to be engaged critics who recognized the nuances of cultivated performances. Copyright © The Author(s), 2021. Published by Cambridge University Press.
Keywords: dept.his; peer-reviewed

Book Review: The keepers of the seas the blue age gregg easterbrook PublicAffairs, 2021. 304 pp. - Smith, Jason W. (Science (New York, N.Y.), 2021)
Keywords: article; book.review; dept.his

Understanding the role of wrongdoing in technological disasters: Utilizing ecofeminist philosophy to examine commemoration. - Roe, Sarah M.; Zavar, Elyse (Studies in history and philosophy of science, 2021)
Stemming from human accident, error, or neglect, technological disasters, such as chemical spills, toxic waste contamination, nuclear radiation, transportation accidents, and factory explosions, are products of the modern industrial complex. Toxic contamination of the land can permanently displace people from their homes and erase places from the landscape. Commemoration provides an opportunity to remember the past and celebrate culturally significant place attachments while contributing to the recovery process by aiding in community healing after devastating events. We focus on two key components regarding commemoration after technological disaster, namely the acknowledgement of wrongdoing and the celebration of a resilient population and landscape. We argue that a combination of ecofeminist philosophy and environmental justice frameworks allows for a better understanding of the cycle of disaster and mitigation as it pertains to targeted groups, and that commemorative acts and artifacts following human-made disasters often fail to successfully reform this cycle. Moreover, the combination of ecofeminist philosophy and environmental justice allows us to examine the complex relationship between responsibility and targeted groups through disaster commemoration, which serves as an important way to communicate wrongdoing to both the local and greater population. Through engagement with ecofeminist philosophy and environmental justice frameworks, we explicate how commemoration after technological disaster can disrupt or reinforce systematic inequalities. © 2021 Elsevier Ltd
Keywords: article; artifact; contamination; dept.his; disaster; explosion; factory; human; justice; neglect; peer-reviewed; philosophy; responsibility; toxic waste

Storm of the Sea: Indians & Empires in the Atlantic's Age of Sail - Smith, Jason W. (Journal of American Studies, 2020)
Keywords: dept.his; peer-reviewed

Preserving Maritime America: A Cultural History of the Nation's Great Maritime Museums - Smith, Jason W. (New England Quarterly-a Historical Review of New England Life and Letters, 2020)
Keywords: dept.his

Guatemala's Catholic Revolution: A History of Religious and Social Reform, 1920-1968. - Kordick, Carmen (Americas, 2020)
Keywords: dept.his; peer-reviewed

They're going to kill me there. Culture, violence and the Cold War in Costa Rica (1979-1990) - Kordick, Carmen (Americas, 2020)
Keywords: dept.his; peer-reviewed

Indochina - Thompson, C. Michele (Cambridge History of Science, Vol 8: Modern Science in National, Transnational, and Global Context, 2020)
Keywords: dept.his

Plenty of barbarians, but no bird's milk: The depiction of Russia in German school books, 1890-1914 - Paddock, Troy R. E. (Internationale Schulbuchforschung, 1998)
This article examines the description of Russia in German history and geography textbooks. Nineteenth-century German pedagogical theory linked the natural sciences and the human sciences; the connection supplies further evidence of the perceived organic nature of the nation-state. Although regional and confessional differences among the German states affected the description of German history, the depiction of Russia was consistent. Russia was depicted as a barbaric, backward, and Asiatic empire. The implicit, and often explicit, comparison in the texts was between Russia and Germany. The description of a foreign power served to reinforce German national identity. Moreover, an examination of German geography and history textbooks reveals striking similarities between the perception of Russia in Germany and the Anglo-French depiction of the Near East. Dieser Aufsatz befaßt sich mit dem Rußlandbild in deutschen Schulbüchern für Geschichte und Geographie. Deutsche Pädagogik im 19. Jahrhundert verband die Naturwissenschaft mit der Geisteswissenschaft; diese Verbindung ist noch ein Beweis für die Auf- fassung des Nationalstaats als organisches Wesen. Obwohl regionale und konfessionelle Unterschiede unter den deutschen Ländern die Darstellung von deutscher Geschichte beeinflußten, war die Schilderung von Rußland übereinstimmend. Rußland wurde als ein barbarisches, rückständiges, asiatisches Reich gezeichnet. Der unausgesprochene, und manchmal doch ausgesprochene Vergleich in den Büchern galt Deutschland und Rußland. Die Darstellung der fremden Macht verstärkte die deutsche Nationalidentität. Außerdem enthüllt eine Untersuchung der Schulbücher überraschende Ähnlichkeiten zwischen der deutschen Beschreibung von Rußland und den englischen und französischen Darstellungen des Nahen Osten. L'auteur de cet article analyse l'image de la Russie dans les manuels scolaires allemands d'histoire et de géographie. La pédagogie allemande du 19ème siècle faisait le lien entre les sciences naturelles et les sciences humaines; cette association fournit une preuve supplémentaire du fait que l'Etat-nation était perçu comme un organisme vivant. Alors que les différences régionales et confessionnelles existant entre les différents Etats allemands influençaient la présentation de l'histoire allemande, la description de la Russie était concordante. La Russie était dépeinte comme un empire barbare, arriéré et asiatique. La comparaison implicite, et souvent explicite des textes scolaires concernait la Russie et l'Allemagne. La représentation d'une puissance étrangère servait à renforcer l'identité allemande. En outre, l'analyse de ces manuels révèle des ressemblances étonnantes entre la perception de la Russie et les portraits français et anglais du Proche-Orient.
Keywords: dept.his; ⛔ No DOI found

Dobra ruska miza, slaba ruska miza - Thomas Mann in nemški orientalizem - Paddock, Troy R. E. (Borec, 2004)
Keywords: dept.his; ⛔ No DOI found

Rethinking Friedrich Meinecke's historicism - Paddock, Troy R. E. (Rethinking History, 2006)
This essay revisits the work of the German historian Friedrich Meinecke and offers new interpretation of his major works, Weltbürgertum und Nationalstaat (1907), Die Ideen der Staatsräson in der neuen Geschichte (1924), and Die Entstehung des Historismus (1936). The standard interpretation of Meinecke's work maintains that World War I caused a break in his thinking and caused him to rethink the role of power in the state. By stressing the first half of Weltbürgertum rather than the second, this article delineates a continuity of Meinecke's thought and points to the limitations of historicism as a historical narrative. It offers a possible explanation for how the conservative implications in the thought of an individual, who personally and politically was a Vernuftrepublikaner, could escape the author himself. This article also discusses what could be called the classical liberal critique of Meinecke's historicism, points to some of its limitations, and offers a more measured criticism of Meinecke that examines him on his own terms—and finds him wanting.
Keywords: Classical liberalism; Historicism; Historiography; Meinecke; Natural law; State; dept.his

Bridges: Technology and the Social - Paddock, Troy R. E. (Environment, Space, Place, 2010)
Keywords: dept.his

Teaching the Great War through Peace - Shortell, Catherine K.; Paddock, Troy R. E. (The History Teacher, 2011)
Keywords: dept.his; ⛔ No DOI found

“No Man’s Land”: Forbidden and Subversive Space in War - Paddock, Troy R. E. (Environment, Space, Place, 2013)
Keywords: dept.his

Building within space: thoughts towards an environmental ethics - Paddock, Troy (Ethics in Progress, 2014)
The need for constructing an environmental ethics that keeps sustainability in mind is the result of a collision of the realization that the natural environment is neither limitless nor impervious to actions with a view of nature that has been fundamentally instrumentalist and anthropocentric. This paper will borrow from architectural theory in an effort to do two things: First, it will point to some of the limitations of an anthropocentric view of nature and how it impacts efforts to influence environmental policy; second, it will suggest that ideas from Aristotle and Actor Network Theory can help to provide a paradigm within which we can think about nature in a way that offers an alternative framing of questions about the environment.
Keywords: dept.his

Performing Politics - Paddock, Troy R. E. (Contemporary Aesthetics, 2015)
Walter Benjamin’s observation that fascism turns politics into aesthetics is, by now, a well-worn idea. This article argues that Benjamin’s critique of politics can apply just as much to the modern democratic politics of the United States. Borrowing from Benjamin, Jürgen Habermas, and Carl Schmitt, this article suggests that modern political discourse in the United States does not follow the classical liberal ideal of rational discourse in the marketplace of ideas within the public sphere. Instead, contemporary politics has become spectacle where images and slogans replace thought and debate in a 24/7 news cycle and political infotainment programs. The result is that progressives and conservatives have their own political “ecospheres” which enable them to have their own perspective reinforced, and debate is replaced by straw man arguments and personal attacks.
Keywords: dept.his; ⛔ No DOI found

Spatial relations and the struggle for space: Friedrich Ratzel’s impact on German education from the Wilhelmine Empire to the Third Reich - Paddock, Troy (Journal of Educational Media, Memory, and Society, 2016)
This article examines the influence of Friedrich Ratzel’s idea of the struggle for space and its impact on cultural and national development depicted in German geography and history textbooks from the Wilhelmine era to the Third Reich. Ratzel’s concept of bio-geography conceived the state as a living organism that is the product of humanity’s interaction with the land and also facilitates humanity’s spread across the earth. German textbooks promoted a similar concept of the state in their portrayal of geography and history, the implications of which were appropriated by the National Socialists to support their geopolitical goals.
Keywords: Education; Friedrich ratzel; Geography instruction; History instruction; National identity; State; Textbooks; dept.his

Historiker als Politiker - Paddock, Troy R. E. (Russen und Russland aus deutscher Sicht: 19./20. Jahrhundert: Von der Bismarckzeit bis zum Ersten Weltkrieg, 2000)
Reprinted in Zauber und Abwehr. Aur Kultutgeschichte der deutsch-russiachen Beziehungen, Dagmar Hermann and Mechthild Keller, eds. (Wilhelm Fink Verlag, 2003)
Keywords: dept.his

Land makes the man: topography and national character in german school books - Paddock, Troy R. E. (Lived topographies and their mediational forces, 2005)
"This collection explores the various forms of narrative, semiotic, and technological mediation that shape the experience of place. From the East End of London to Navajo lands to Ground Zero, Lived Topographies examines the great effect of language, mass media, surveillance, and other incursions of the contemporary world on topographical experience and description. Gary Backhaus and John Murungi have assembled a wide array of scholars to provide an interdisciplinary approach to this subject, giving this collection a unique perspective on the phenomenology of place."--Jacket.
Keywords: dept.his

Chronoscapes/chronos escapes: a meditation on historical time - Paddock, Troy R. E. (Ecoscapes: geographical patternings of relations, 2006)
Keywords: dept.his

Is one world enough for all of us?: Thoughts on globalization - Paddock, Troy R. E. (Dangers in the incommensurability of globalization: socio-political volatilities, 2008)
Keywords: dept.his

A Call to Arms: Propaganda, Public Opinion, and Newspapers in the Great War - Paddock, Troy R. E. (Perspectives on the twentieth century, 2004)
World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t., World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t
Keywords: Press coverage; Propaganda; World War, 1914-1918; Public opinion; Press and propaganda; War; World War, 1914-1918; dept.his; faculty_collection

Creating the Russian Peril: Education, the Public Sphere, and National Identity in Imperial Germany, 1890-1914 - Paddock, Troy R. E. (Camden House, 2010)
German attitudes toward and stereotypes of Russia before the First World War and how they were inculcated in the public.
Keywords: 1871-1918; 19th century; Education; 19th century; Nationalism; 20th century; Germany; 20th century; Nationalism; Foreign public opinion, German; Russia; Germany; Germany; Germany; Germany; Russia; History; History; Education; Political aspects; Press coverage; Public opinion; Relations; Russia; Russia; SCSU Faculty Scholar Award; award_winner; dept.his; faculty_collection

World War I and Propaganda - Paddock, Troy R. E. (History of warfare, 2014)
World War I and Propaganda offers a new look at a familiar subject. The contributions to this volume demonstrate that the traditional view of propaganda as top-down manipulation is no longer plausible. Drawing from a variety of sources, scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted. Propaganda was tailored to meet local circumstances and integrated into a larger narrative in which the war was not always the most important issue. Issues centering on local politics, national identity, preservation of tradition, or hopes of a brighter future all played a role in different forms of propaganda. Contributors are Christopher Barthel, Donata Blobaum, Robert Blobaum, Mourad Djebabla, Christopher Fischer, Andrew T. Jarboe, Elli Lemonidou, David Monger, Javier Pounce,Catriona Pennell, Anne Samson, Richard Smith, Kenneth Andrew Steuer, María Inés Tato, and Lisa Todd.
Keywords: dept.his

Notes on the state of Virginia: an annotated edition - Jefferson, Thomas; Forbes, Robert Pierce (Yale University Press, 2021)
Keywords: Description and travel; Early works to 1800; Early works to 1800; Virginia; History; Virginia; dept.his; faculty_collection

Abolition and Antislavery: United States - Forbes, Robert P. (A Historical Guide to World Slavery, 1998)
Eminent scholars provide an overview of what we now know about slavery as an institution and way of life in cultures around the globe from ancient times to the present day. Drawing on the virtual explosion of empirical research and theoretical discussion on the subject over the past thirty years, many of the articles overturn conventional wisdom and illuminate little-known aspects of the subject, with essays on topics such as concubinage, eunuchs, and occupational mobility.
Keywords: dept.his

Slavery and the Evangelical Enlightenment - Forbes, Robert Pierce (Religion and the Antebellum Debate Over Slavery, 1998)
Keywords: 19th century; 19th century; Slavery; History; History / United States / 19th Century; Slavery and the church; Social Science / Ethnic Studies / African American Studies; Social Science / Sociology of Religion; United States; dept.his; faculty_collection

Francis Kernan: The Life and Times of a 19th Century, Citizen-Politician of Upstate New York - Kernan, Karen Clemens; Kernan, John Devereux; Forbes, Robert P. (Oneida County Historical Society, 1999)
Keywords: dept.his

"Foreword," special issue on "New Perspectives on the Transatlanic Slave Trade - Forbes, Robert P.; Davis, David Brion (William & Mary Quarterly, 2005)
Keywords: dept.his; ⛔ No DOI found

'Truth Systematised’: The Changing Debate over Slavery and Abolition - Forbes, Robert P. (Prophets of Protest: Reconsidering the History of American Abolitionism, 2006)
The first collection of original contributions on American abolitionism to appear in a generation.The campaign to abolish slavery in the United States was the most powerful and effective social movement of the nineteenth century and has served as a recurring source of inspiration for every subsequent struggle against injustice. But the abolitionist story has traditionally focused on the evangelical impulses of white, male, middle-class reformers, obscuring the contributions of many African Americans, women, and others.Prophets of Protest, the first collection of writings on abolitionism in more than a generation, draws on an immense new body of research in African American studies, literature, art history, film, law, women's studies, and other disciplines. The book incorporates new thinking on such topics as the role of early black newspapers, anti-slavery poetry, and abolitionists in film and provides new perspectives on familiar figures such as Sojourner Truth, Louisa May Alcott, Frederick Douglass, and John Brown.With contributions from the leading scholars in the field, Prophets of Protest is a long overdue update of one of the central reform movements in America's history.
Keywords: dept.his

The Missouri Compromise and Its Aftermath: Slavery and the Meaning of America - Forbes, Robert P. (University of North Carolina Press, 2007)
Robert Pierce Forbes goes behind the scenes of the crucial Missouri Compromise, the most important sectional crisis before the Civil War, to reveal the high-level deal-making, diplomacy, and deception that defused the crisis, including the central, unexpected role of President James Monroe. Although Missouri was allowed to join the union with slavery, the compromise in fact closed off nearly all remaining federal territories to slavery.When Congressman James Tallmadge of New York proposed barring slavery from the new state of Missouri, he sparked the most candid discussion of slavery ever held in Congress. The southern response quenched the surge of nationalism and confidence following the War of 1812 and inaugurated a new politics of racism and reaction. The South's rigidity on slavery made it an alluring electoral target for master political strategist Martin Van Buren, who emerged as the key architect of a new Democratic Party explicitly designed to mobilize southern unity and neutralize antislavery sentiment. Forbes's analysis reveals a surprising national consensus against slavery a generation before the Civil War, which was fractured by the controversy over Missouri.
Keywords: dept.his

The Missouri Controversy and Sectionalism - Forbes, Robert P. (Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson, 2008)
In 1815 the United States was a proud and confident nation. Its second war with England had come to a successful conclusion, and Americans seemed united as never before. The collapse of the Federalist party left the Jeffersonian Republicans in control of virtually all important governmental offices. This period of harmony—what historians once called the Era of Good Feeling—was not illusory, but it was far from stable. One-party government could not persist for long in a vibrant democracy full of ambitious politicians, and sectional harmony was possible only as long as no one addressed the hard issues: slavery, race, western expansion, and economic development.Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson inaugurates a new series for the United States Capitol Historical Society, one that will focus on issues that led to the secession crisis and the Civil War. This first volume examines controversies surrounding sectionalism and the rise of Jacksonian Democracy, placing these sources of conflict in the context of congressional action in the 1820s and 1830s. The essays in this volume consider the plight of American Indians, sectional strife over banking and commerce, emerging issues involving slavery, and the very nature of American democracy.“It is to be regretted that the rich and powerful too often bend the acts of government to their selfish purposes…. There are no necessary evils in government. Its evils exist only in its abuses. If it would confine itself to equal protection, and, as Heaven does its rains, shower its favors alike on the high and the low, the rich and the poor, it would be an unqualified blessing. In the act before me there seems to be a wide and unnecessary departure from these just principles.”—Andrew Jackson, Veto Message Regarding the Bank of the United States, July 10, 1832“I consider, then, the power to annul a law of the United States, assumed by one State, incompatible with the existence of the Union, contradicted expressly by the letter of the Constitution, unauthorized by its spirit, inconsistent with every principle on which it was founded, and destructive of the great object for which it was formed.”—Andrew Jackson, Proclamation Regarding Nullification to the People of South Carolina, December 10, 1832
Keywords: dept.his

Trust and Violence in Atlantic History: The Economic Worlds of Venture Smith - Forbes, Robert P.; Richardson, David; Chandler, B. Saint (Venture Smith and the Business of Slavery and Freedom, 2010)
Keywords: dept.his

Eliade, Joyce, and the Terror of History - Forbes, Robert P. (CrossCurrents, 1986)
Keywords: dept.his; ⛔ No DOI found

Connecticut Connections: African American Sites in Connecticut: A Laboratory for the History of Slavery and Human Rights - Forbes, Robert P. (Connecticut History Review, 2005)
Keywords: dept.his; ⛔ No DOI found

“The Cause of This Blackness”: The Early American Republic and the Construction of Race - Forbes, Robert Pierce (American Nineteenth Century History, 2012)
Race is routinely defined as “socially constructed,” from which it follows that there was a time before its construction. What that time looked like, and how Africans were then viewed by white Americans, is difficult to perceive from a vantage point within the paradigm of race. This essay considers important but neglected cultural referents to argue that a binary distinction between black and white did not emerge on theoretical grounds until the 1780s, when Jefferson's Notes on the State of Virginia shrewdly redirected growing challenges to slavery into quasi-metaphysical reflections on the gulf between whites and blacks.
Keywords: Thomas Jefferson; dept.his; race

"Grating the Nutmeg: Slavery, Race and Sectionalism in Connecticut from the Colonial Era to the Civil War" - Forbes, Robert Pierce (Connecticut History, 2013)
Keywords: dept.his; ⛔ No DOI found

’We Here Highly Resolve’: The End of Compromise and the Return of Revolutionary Time - Forbes, Robert Pierce (Conceived in Liberty: Perspectives on Lincoln at Gettysburg, 2015)
Keywords: dept.his

The Rumble in the Jungle: Muhammad Ali and George Foreman on the Global Stage - Rondinone, Troy (Journal of American History, 2020)
Keywords: dept.his; peer-reviewed

The russian holy synod and the greeks: Reconsidering greek-russian relations in the early modern period (16th–18th centuries) - Chrissidis, Nikolaos A. (Canadian-American Slavic Studies, 2020)
The article first surveys Greek interpretations of the creation of the Russian Holy Synod by Peter the Great. It provides a critical assessment of the historiographical paradigm offered by N.F. Kapterev for the analysis of Greek-Russian relations in the early modern period. Finally, it proposes that scholars should focus on a Greek history of Greek-Russian relations as a complement and possibly corrective to the Kapterev paradigm. © verlag ferdinand schöningh, 2020.
Keywords: Aleksander stourdza; Greek-russian relations; Konstantin oinonomos; Nikolai kapterev; Peter the great; Russian holy synod; dept.his; peer-reviewed

Socio/Psycholinguistics of the cultural revolution: an empirical study - London, Ivan D.; Lee, Ta-Ling (Psychological Reports, 1977)
Keywords: dept.his

Review of Desperate Diplomacy: William H. Seward's Foreign Policy, 1861 - Farnham, Thomas J. (The Journal of Southern History, 1977)
Keywords: dept.his

War and Government in Habsburg Spain, 1560-1620 - Thompson,iaa - Stewart, P (American Historical Review, 1977)
Keywords: dept.his

Book Review: E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35 - Cone, L. Winston (Journal of Asian and African Studies, 1975)
"E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35" published on 01 Jan 1975 by Brill.
Keywords: book.review; dept.his

Works of Williams,r,sir - Evans,jx - Stewart, P (American Historical Review, 1973)
Keywords: dept.his

Review of The Birth of Modern America, 1820-1850 - Farnham, Thomas J. (The Journal of Southern History, 1972)
Keywords: dept.his

Devaldes,j and Origins of Spanish and Italian Reformation - Spanish - Nieto,jc - Stewart, P (American Historical Review, 1971)
Keywords: dept.his

Review of The Era of Expansion: 1800-1848 - Farnham, Thomas J. (The Journal of Southern History, 1969)
Keywords: dept.his

Book Review: Gamaliel bailey and antislavery union. by stanley harrold. (kent: kent state university press, 1986. xvi + 301 pp. 28.00.) - Davis, Hugh (The Journal of American History, 1988)
Keywords: book.review; dept.his

Review of Explaining Religion: Criticism and Theory from Bodin to Freud - Ausmus, Harry J. (The American Historical Review, 1988)
Keywords: dept.his

Review of Henry David Thoreau: A Life of the Mind, Robert D. Richardson, Jr - Caruthers, J. Wade; Richardson, Robert D. (The American Historical Review, 1987)
Keywords: dept.his

Review of Religion in the Age of Romanticism: Studies in Early Nineteenth-Century Thought - Ausmus, Harry J. (The American Historical Review, 1986)
Keywords: dept.his

Review of The Seven Day Circle: The History and Meaning of the Week - Ausmus, Harry J. (The American Historical Review, 1986)
Keywords: dept.his

Research in South Africa: to know an archive - Feinberg, Harvey M (History in Africa, 1986)
Keywords: dept.his

Review of L'ordre du temps - Ausmus, Harry J. (The American Historical Review, 1985)
Keywords: dept.his

Western religious thought - Ausmus, Harry J (Journal of the American Academy of Religion, 1982)
Keywords: dept.his

Review of Transcendentalism as a Social Movement, 1830-1850 - Caruthers, J. Wade (The American Historical Review, 1982)
Keywords: dept.his

Nuclear-weapons and the future - an unthinkable proposal - Tyler, RL (Humanist, 1982)
Keywords: dept.his; ⛔ No DOI found

Book Review: Revolution and tradition in tientsin, 1949-1952 - lieberthal,kg - Lee, TL (American Historical Review, 1981)
Keywords: book.review; dept.his

High noon in memory lane - the superior reality of the past - Tyler, RL (Humanist, 1981)
Keywords: dept.his; ⛔ No DOI found

An eighteenth-century case of plagiarism: william smith's A new voyage to guinea - Feinberg, Harvey M. (History in Africa, 1979)
Keywords: dept.his

Nietzsche and eschatology - Ausmus, Harry J. (The Journal of Religion, 1978)
Keywords: dept.his

Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
Keywords: book.review; dept.his

Review of The Encyclopaedia Africana Dictionary of African Biography, Volume I: Ethiopia-Ghana - Feinberg, Harvey M. (The International Journal of African Historical Studies, 1978)
Keywords: dept.his

Plant Liberation - Struggle Against Fauna Chauvinism - Tyler, RL (Humanist, 1978)
Keywords: dept.his; ⛔ No DOI found

Review of Trade and Economic Change on the Gold Coast, 1807-1874 - Feinberg, H.M. (The International Journal of African Historical Studies, 1977)
Keywords: dept.his

Schopenhauer's view of history: A note - Ausmus, Harry J. (History and Theory, 1976)
Keywords: dept.his

There Was an Elmina Note, But.... - Feinberg, H.M. (The International Journal of African Historical Studies, 1976)
Keywords: dept.his

Confessions of a Closet Househusband - Tyler, RL (Humanist, 1976)
Keywords: dept.his; ⛔ No DOI found

Review of Akwapim Handbook - Feinberg, H. M. (The International Journal of African Historical Studies, 1975)
Keywords: dept.his

Boredom and Treadmill of Doing - Tyler, RL (Humanist, 1975)
Keywords: dept.his; ⛔ No DOI found

New data on European mortality in West Africa: the Dutch on the Gold Coast, 1719-1760. - Feinberg, Harvey M (The Journal of African History, 1974)
Keywords: dept.his

Review of Colonial Governors from the Fifteenth Century to the Present. A Comprehensive List - Feinberg, H. M. (The International Journal of African Historical Studies, 1973)
Keywords: dept.his

Consciousness Iv - or Let Us Not Envy Young - Tyler, RL (Humanist, 1972)
Keywords: dept.his; ⛔ No DOI found

Old Siwash Is Not Our Beacon - Tyler, RL (Journal of General Education, 1972)
Keywords: dept.his; ⛔ No DOI found

Book Review: Mill town: A social history of everett, washington, from its earliest beginnings on the shores of puget sound to the tragic and infamous event known as the everett massacre. by norman h. clark. (seattle: university of washington press, 1970. x + 267 pp. illustrations, notes, and index. 7.95.) - Tyler, Robert (The Journal of American History, 1972)
Keywords: book.review; dept.his

Review of Benin and the Europeans 1485-1897 - Feinberg, H. M. (African Historical Studies, 1971)
Keywords: dept.his

Review of Trade and Politics on the Gold Coast: 1600-1720. A Study of the African Reaction to European Trade - Feinberg, H. M. (African Historical Studies, 1971)
Keywords: dept.his

Pornos and Prudes Unite - Tyler, RL (Humanist, 1971)
Keywords: dept.his; ⛔ No DOI found

An Incident in Elmina-Dutch Relations, The Gold Coast (Ghana), 1739-1740 - Feinberg, H. M. (African Historical Studies, 1970)
Keywords: dept.his

Review of West African Trade and Coast Society: A Family Study - Feinberg, H. M. (African Historical Studies, 1970)
Keywords: dept.his

2-Marriage Revolving-Mate Generation-Bridging Plan to Save Marriage - Tyler, RL (Humanist, 1970)
Keywords: dept.his; ⛔ No DOI found

Social education looks at history curriculum - 11-year view - Caruthers, J. Wade (Social Education, 1967)
Keywords: dept.his; ⛔ No DOI found

Book Review: Michael r. dutton, policing and punishment in china , london and new york: cambridge university press, 1992. pp. xii, 391. 74.95 (ISBN 0-521-40097-X). - Lee, Taling; Dutton, Michael R (Law and History Review, 1996)
Keywords: book.review; dept.his

A social history of wet nursing in America: From breast to bottle. - Metaxas, VA (Isis, 1999)
Keywords: dept.his

Ghaylan Al-Dimashqi: The isolation of a heretic in Islamic historiography - Judd, SC (International Journal of Middle East Studies, 1999)
Keywords: dept.his

Book Review: War and the illiberal conscience: coker, christopher: boulder: westview press 240 pp., publication date: april 1998 - Paddock, Troy (History: Reviews of New Books, 1999)
Keywords: book.review; dept.his

The Carswell affair: The politics of a Supreme Court nomination in the Nixon administration - Kalk, BH (American Journal of Legal History, 1998)
Keywords: dept.his

Book Review: Barbara Caine. English Feminism, 1780–1980 . New York: Oxford University Press. 1997. Pp. xvii, 336. 19.95 paper. ISBN 0-19-820434-5. - Beals, Polly (Albion, 1998)
Keywords: book.review; dept.his

Still stuck at sevastopol: the depiction of russia during the russo-japanese war and the beginning of the first world war in the german press - Paddock, Troy (German History, 1998)
Keywords: dept.his

The machine in the nursery: incubator technology and the origins of newborn intensive care. - Quiroga, VAM (Isis, 1997)
Keywords: dept.his

Revolutionary outlaws - allen,ethan and the struggle for independence on the early american frontier - bellesiles,ma - Mintz, MM (American Historical Review, 1995)
Keywords: dept.his

South Africa and land ownership: what's in a deed? - Feinberg, Harvey M (History in Africa, 1995)
Keywords: dept.his

Book Review: Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.) - Mintz, Max M. (Journal of American History, 1991)
Max M. Mintz; Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.), Journal of American History,
Keywords: book.review; dept.his

Save the babies - american public-health reform and the prevention of infant-mortality, 1850-1929 - meckel,ra - Quiroga, VAM (Journal of American History, 1991)
Keywords: dept.his; peer-reviewed

Diphtheria and medical therapy in late 19th century New York City - Quiroga, V.A.M. (New York State Journal of Medicine, 1990)
Keywords: Diphtheria; History of Medicine, 19th Cent.; Human; Intubation, Intratracheal; New York City; Portraits; Tracheotomy; article; dept.his; diphtheria; history of medicine; human; priority journal; ⛔ No DOI found

Book Review: abolitionism: A revolutionary movement, by hugh davis - Davis, Hugh (Pennsylvania Magazine of History and Biography, 1990)
Keywords: book.review; dept.his; ⛔ No DOI found

Book Review: Denis Lalande, Jean II le Meingre, dit Boucicaut (1366–1421): Etude d'une biographie héroïque . (Publications romanes et françaises, 184.) Geneva: Droz, 1988. Paper. Pp. ii, 227. - Friedlander, Alan (Speculum, 1990)
Keywords: book.review; dept.his

The venomous course of southwestern opium: Qing prohibition in Yunnan, Sichuan, and Guizhou in the early nineteenth century - Bello, David (The Journal of Asian Studies, 2003)
Keywords: dept.his

Book Review: William chester jordan. unceasing strife, unending fear: jacques de thérines and the freedom of the church in the age of the last capetians. princeton: princeton university press. 2005. pp. xi, 154. 29.95Reviews of books and FilmsEurope: ancient and medieval - Friedlander, Alan (The American Historical Review, 2005)
Keywords: book.review; dept.his

Fighting for a living wage - Rondinone, T (Labor History, 2005)
Keywords: dept.his; ⛔ No DOI found

Book Review: The Rise of Aggressive Abolitionism: Addresses to the Slaves. By Stanley Harrold. (Lexington: University Press of Kentucky, 2004. x, 246 pp. 35.00, isbn 0-8131-2290-2.) - Davis, Hugh (The Journal of American History, 2005)
Keywords: book.review; dept.his

Book Review: Pope John XXII and his Franciscan cardinal. Bertrand de la Tour and the apostolic poverty controversy . By Patrick Nold. (Oxford Historical Monographs.) Pp. xii+212. Oxford: Clarendon Press, 2003. £45. 0 19 926875 4 - Friedlander, Alan (The Journal of Ecclesiastical History, 2005)
Keywords: book.review; dept.his

Book Review: Constitutional failure: Carl Schmitt in Weimar: Kennedy, Ellen: Durham: Duke University Press, 288 pp., publication date: July 2004 - Paddock, Troy (History: Reviews of New Books, 2005)
Keywords: book review; book.review; dept.his

Book Review: Inventing the nation: Germany: Berger, Stefan: New York: Oxford University Press, 274 pp., publication date: July 2000 - Paddock, Troy (History: Reviews of New Books, 2005)
Keywords: book review; book.review; dept.his

Trusteeship and black landownership in the Transvaal during the nineteenth and twentieth centuries - Bergh, J S; Feinberg, Harvey M (African Historical Review, 2004)
Keywords: dept.his

Book Review: Two approaches to introductory middle east history - the middle east: A history , 6th edition, by william ochsenwald and sidney nettleton fisher. new york: McGraw hill, 2004. 780 pages, glossary, index. US59.30 (paper) ISBN 0-07-244233-6 - the levant: A fractured mosaic , by william harris. princeton: marcus weiner, 2003. 211 pages, glossary, index. US22.95 (paper) ISBN 1-55876-265-5 - Judd, Steven (Middle East Studies Association Bulletin, 2004)
Keywords: book.review; dept.his

Chosen peoples: sacred sources of national identity - Paddock, Troy (History: Reviews of New Books, 2004)
Keywords: dept.his

Gedachtes wohnen: Heidegger and cultural geography - Paddock, Troy (Philosophy & Geography, 2004)
Keywords: cultural geography; dept.his

Imagining the nation in nature: landscape preservation and German identity, 1885–1945: Lekan, Thomas M.: Cambridge, MA: Harvard University Press, 334 pp., publication date: February 2004 - Paddock, Troy (History: Reviews of New Books, 2004)
Keywords: book review; dept.his

The german empire on the brink. the daily-telegraph affair and hale-interview of 1908: an account and documentation - Paddock, TRE (German Studies Review, 2003)
Keywords: dept.his

James Monroe: Oberlin's Christian statesman & reformer, 1821-1898. - Davis, Hugh (The Journal of American History, 2003)
Keywords: dept.his; peer-reviewed

Book Review: Arabia and the Arabs: From the Bronze Age to the Coming of Islam , by Robert G. Hoyland. 324 pages, bibliography, index. New York: Routledge, 2001. 23.95 (Paper) ISBN 0-415-19535-7 - Judd, Steven (Middle East Studies Association Bulletin, 2003)
Keywords: book.review; dept.his

The historiography of american violence - Leonard, Ira M; Leonard, Christopher C (Homicide Studies, 2003)
Historians have generally agreed that the United States has always been an extremely violent nation; however, since the 1950s they have been myopic in their treatment of violence in America and have not provided the American people with essential information about their society and culture. Those historians who focused on violence in America, until the 1990s, have focused on only one form of violence—collective social violence. Largely overlooked, and equally significant, are interpersonal violence (including criminal and domestic violence) and the effect of war. This deficiency helps explain why Americans seem genuinely at a loss to understand the nature, character, and frequency of violence in America's past and present, especially when a high-profile violent incident occurs. This article surveys the historiography of violence in America through the 1990s and examines the contributions of historians and legal scholars who have focused on interpersonal and criminal violence. © 2003, SAGE Publications. All rights reserved.
Keywords: dept.his; historiography; lynching; riots; vigilantism

Book Review: Inventing the schlieffen plan: German war planning 1871–1914: Zuber, Terence: Oxford: Oxford University Press 340 pp., publication date: January 2003 - Paddock, Troy (History: Reviews of New Books, 2003)
Keywords: book review; book.review; dept.his

A gentleman of color: The life of James Forten. - Davis, H (American Historical Review, 2002)
Keywords: dept.his

Julie winch. A gentleman of color: the life of james forten. new york: oxford university press. 2002. pp. x, 501. 35.00 - Davis, Hugh (The American Historical Review, 2002)
Keywords: Review; dept.his

The pennsylvania state equal rights league and the northern black struggle for legal equality, 1864-1877 - Davis, Hugh (Pennsylvania Magazine of History and Biography, 2002)
Keywords: dept.his; ⛔ No DOI found

Book Review: Cool conduct: the culture of distance in weimar germany: lethen, helmut: trans. don reneau, berkeley: university of california press, 263 pp., publication date: december 2001 - Paddock, Troy (History: Reviews of New Books, 2002)
Keywords: book.review; dept.his

Book Review: The politics of education: teachers and school reform in Weimar Germany - Paddock, Troy (History: Reviews of New Books, 2002)
Keywords: book.review; dept.his

Parker pillsbury: radical abolitionist, male feminist. - Davis, H (American Historical Review, 2001)
Keywords: dept.his

Rereading German history: From unification to reunification, 1800-1996 - Paddock, TRE (German Studies Review, 2000)
Keywords: dept.his

A doctor of their own: The history of adolescent medicine. - Metaxas, V (Isis, 2000)
Keywords: dept.his

Eleanor Clarke Slagle and Susan E. Tracy: Personal and professional identity and the development of occupational therapy in progressive era America - Metaxas, VA (Nursing History Review, 2000)
Keywords: *Occupational Therapy/hi [History]; *Professional Autonomy; Female; History, 20th Century; Humans; Job Description; Societies, Scientific/hi [History]; United States; Women's Rights/hi [History]; Women, Working/hi [History]; dept.his

Book Review: The crisis of reason: european thought, 1848–1914: burrow, j. w.: new haven: yale university press, 269 pp., publication date: october 2000 - Paddock, Troy (History: Reviews of New Books, 2000)
Keywords: book.review; dept.his

Book Review: The social history of the third reich, 1933–1945: ayçoberry, pierre: trans. janet lloyd, new york: the new press, 380 pp., publication date: october 1999 - Paddock, Troy (History: Reviews of New Books, 2000)
Keywords: book.review; dept.his

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography

South African territorial segregation: new data on African farm purchases, 1913-1936 - Feinberg, Harvey M; Horn, Andre C (The Journal of African History, 2009)
By using new sources and a complementary historical and geo-analytical approach, this article Illustrates that the Natives Land Act (no. 27 of 1913) failed to stop Africans from buying land. New evidence demonstrates that African land ownership outside the reserves in the Transvaal actually increased after 1913. This evidence leads to a deeper questioning of the extent to which the South African government was able to impose rural territorial segregation by 1936 and reveals the limits of white power in the early Union period.
Keywords: Archives; Land; Law; Race; South Africa; apartheid; dept.his; historical geography; land tenure; landownership; legislation; racial segregation

Semblance of Sovereignty: Cartographic Possession in Map Cartouches and Atlas Frontispieces of Early Modern Europe - Petto, Christine M. (Symbolic Landscapes, 2009)
Maps always present an interpretation of reality and always carry distortions, some of which are consciously or unconsciously ideological. The geographicity of mapping, which involves an intertwining of both science and art, is a vehicle for spatialized/spatializing interpretations of an actual spatiality, and as such is a catalyst for enacting further spatial productions on the basis of the capacity of maps to project themselves “into the landscape.” The scientific pretensions of mapping serve to veil the character of their projective enactment. Maps always entail virtual embodiment, that is, maps realize one possibility out of many, even in the most mathematically “accurate” of spatial relations. Thus, if the imaginative involves both embodied schema and virtual embodiments, we cannot dismiss the role of the geography of imagination in a dialectical relation with the geography of perception, of the actual. The symbolic function of cartouches and frontispieces provides an imagineering context of constructing reality on the basis of the symbolization.
Keywords: Facsimile Edition; Manuscript Library; Online Collection; United Province; Virtual Embodiment; dept.his

Guarding the switch: cultivating nationalism during the pullman strike - Rondinone, Troy (The Journal of the Gilded Age and Progressive Era, 2009)
The Pullman Strike of 1894 was a cataclysmic event for the nation. During its violent course, the print media provided an interpretive frame that portrayed the strike in large measure as an immigrant-inspired attack on American laws and democratic customs. Often characterizing the strikers as “foreigners” in the thrall of anarchist ideologies and a tyrannous labor chieftain, journalists painted a stark picture indeed. Employing framing theory, Gramsci's notion of hegemony, and recent insights on the ethnic quality of nationalism, this essay argues that newspapers and other major print periodicals significantly contributed to the formation of nationalist attitudes at a time when many Americans were deeply worried over the direction in which the country was headed. © 2009, Society for Historians of the Gilded Age and Progressive Era. All rights reserved.
Keywords: dept.his

Review of The vaccinators: smallpox, medical knowledge, and the "Opening" of japan - Thompson, C Michele (Bulletin of the History of Medicine, 2009)
Keywords: book.review; dept.his

Charles Eliot Norton: The art of reform in nineteenth-century America - Davis, Hugh (The Journal of American History, 2008)
Keywords: dept.his; peer-reviewed

Technology and the culture of modernity in Britain and Germany 1890-1945. - Paddock, Troy (German studies review, 2007)
Keywords: dept.his; ⛔ No DOI found

Beasts of the field: A narrative history of California farmworkers, 1769-1913 - Rondinone, Troy (Labor History, 2006)
Keywords: dept.his; ⛔ No DOI found

Wilhelminism and its legacies: German modernities, imperialism and the meanings of reform, 1890-1930. - Paddock, T (German Studies Review, 2006)
Keywords: dept.his; ⛔ No DOI found

Democratic discourses: the radical abolition movement and antebellum american literature - Davis, Hugh (The Journal of American History, 2006)
Keywords: dept.his; peer-reviewed

On the provenance of the holy shroud of Lirey/Turin: A minor suggestion - Friedlander, Alan (The Journal of Ecclesiastical History, 2006)
Keywords: dept.his

Creating an oriental feindbild - Paddock, Troy (Central European History, 2006)
Keywords: dept.his

Review of Ceramic technology, part XII of chemistry and chemical technology - Thompson, C. Michele (History and Philosophy of the Life Sciences, 2006)
Keywords: book.review; dept.his; ⛔ No DOI found

The threat from the east - Paddock, Troy (The Central Powers in Russia's Great War and Revolution, 1914-22: enemy visions and encounters, 2020)
"This multiauthor collection of essays analyzes Russia's Great War and Revolution from the perspective of the Central Powers and their encounters with Russia and the Revolution. The peoples of the Central Powers, from elites to civilians, understood the violent clash of armies in a variety of ways. Essays highlight the variety of military and civilian experiences and deal with topics of how soldiers, civilians, and intellectuals perceived Russia and how these understandings translated into security goals, utopian plans for conquered territories, and interethnic violence."--
Keywords: 1894-1917; 20th century; Central Powers (1914-1918); Europe, Eastern; Historiography; History; History, Military; Politics and government; Revolution, 1917-1921; Russia; Soviet Union; World War, 1914-1918; dept.his

The political economy of mexico's independence heroes: selling public history in san miguel de allende - Covert, Lisa Pinley (The Latin Americanist, 2010)
Keywords: dept.his; peer-reviewed

Sexual violence and the military - Cyr, Heather D. (The Wiley Blackwell Encyclopedia of Gender and Sexuality Studies - Sexual Violence and the Military, 2016)
Keywords: dept.his; law; military; sexual assault; sexual harassment; sexual violence

Book Review: The guatemala reader: history, culture, politics - Vrana, Heather (Ethnohistory, 2016)
Keywords: book.review; dept.his

Book Review: Histories of health in southeast asia: perspectives on the long twentieth century. - Thompson, C. Michele (Pacific Affairs, 2016)
Keywords: book.review; dept.his; ⛔ No DOI found

Captured on the gold coast: “Illegal” enslavement, freedom and the pursuit of justice in dutch courts, 1746–1750 - de Kok, Gerhard; Feinberg, Harvey M. (Journal of Global Slavery, 2016)
In May of 1746, slaving captain Christiaan Hagerop illegally captured ten Gold Coast canoe paddlers, seven of whom were free Africans from Elmina and Fante. Hagerop subsequently sailed to Suriname, where he sold the paddlers into slavery. To appease the relatives of the captured men and to safeguard its reputation among local Africans, the Dutch West India Company (WIC) launched a search for the kidnapped paddlers. Six of the men were eventually located in Suriname in 1749, the seventh having died in slavery. While the Africans were transported back to the Gold Coast via Amsterdam, the WIC tried to have Hagerop extradited to its Gold Coast possessions to receive punishment for his crime. A legal battle over jurisdictional competence ensued in the Dutch Republic, the outcome of which was that the captain was made to stand trial in Amsterdam, but in the end he received very little punishment. © 2016 Copyright 2016 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: Africa; Gold Coast; Slave Trade; Suriname; dept.his; wic

Book Review: RECEPTION OF WAR. A.S. bradford) war. antiquity and its legacy. pp. xvi + 176, maps. new york: oxford university press, 2015. cased. ISBN: 978-0-19-538090-3 (978-0-19-538091-0 pbk). - Nakamura, Byron (Classical Review, 2016)
Keywords: book.review; dept.his

The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.his

Book Review: Mohammad rihan: the politics and culture of an umayyad tribe: conflict and factionalism in the early islamic period . viii, 231 pp. london and new york: I.B. tauris, 2014. £58. ISBN 978 1 78076 564 8. - Judd, Steven (Bulletin of The School of Oriental and African Studies-university of London, 2015)
Keywords: book.review; dept.his

The early qadariyya - Judd, Steven C. (The Oxford Handbook of Islamic Theology, 2014)
This article discusses the briefly significant Qadariyya movement during the Umayyad period, with an emphasis on how the movement and its adherents were treated in later sources. The article examines the doctrine of human free will advocated by the Qadariyya, exploring the impetus behind their theological viewpoints and the doctrinal complications that accompanied human free will. It also addresses the debate about the origins of both the doctrine and the movement, and the significance of accusations of Christian roots. The article discusses the views ascribed to prominent Qadari leaders, including Maʿbad al-Juhanī and Ghaylān al-Dimashqī, as well as the systematic persecution of the Qadariyya, led by al-Awzāʿī. It also examines the politicization of the Qadariyya and their entanglement with Yazīd (III) b. al-Walīd’s rebellion during the third fitna. Finally, the article addresses the eclipse of the Qadariyya by the Muʿtazilites.
Keywords: dept.his

Reimagining indian country: native american migration and identity in twentieth-century los angeles. - Amerman, Stephen (Journal of American History, 2014)
Keywords: dept.his; peer-reviewed

The indian school on magnolia avenue: voices and images from sherman institute - Amerman, Steve (Ethnohistory, 2014)
Keywords: dept.his

Religious Scholars and the Umayyads: Piety-Minded Supporters of the Marwānid Caliphate - Judd, Steven C. (Culture and civilisation in the Middle East, 2014)
Keywords: Doctrines; History; Judges (Islamic law); History; Muslim scholars; Islamic law; SCSU Faculty Scholar Award; Umayyad dynasty; Islam; award_winner; dept.his; faculty_collection

Map worlds: A history of women in cartography. by will c. van den hoonard - Petto, Christine M (Imago Mundi, 2014)
Keywords: dept.his

Book Review: Jack Johnson, rebel sojourner: boxing in the shadow of the global color line - Rondinone, Troy (International Journal of the History of Sport, 2014)
Keywords: book.review; dept.his

Book Review: A nation of deadbeats: an uncommon history of america's financial disasters - Rondinone, Troy (The Journal of American History, 2013)
Keywords: book.review; dept.his

The caliph and the heretic: ibn sabaʾ and the origins of shī’ism, by sean w. anthony - Judd, Steven C. (Information Systems, 2013)
Keywords: dept.his

A cartel that lasts for centuries: the case of the eastern orthodox church indulgences - Axarloglou, Kostas; Cabolis, Christos; Chrissidis, Nikolaos A (DUTH Research Papers in Economics, 2012)
Keywords: dept.his

Book Review: Lisa fetheringill zwicker. dueling students: conflict, masculinity, and politics in german universities, 1890–1914. (social history, popular culture, and politics in germany.) ann arbor: university of michigan press. 2011. pp. ix, 296. 75.00 - Paddock, Troy (The American Historical Review, 2012)
Keywords: book.review; dept.his

Red power rising: the national indian youth council and the origins of native activism - Amerman, Steve (The Journal of American History, 2011)
Keywords: dept.his; peer-reviewed

Education beyond the mesas: hopi students at sherman institute, 1902–1929 - Amerman, Steve (Western Historical Quarterly, 2011)
Keywords: dept.his

Muhammad and the believers: at the origins of islam. by fred m. donner - Judd, Steven (Journal of the American Academy of Religion, 2011)
Keywords: dept.his

Muslim Persecution of Heretics during the Marwānid Period (64–132/684–750) - Judd, Steven (Al-Masaq: Journal of the Medieval Mediterranean, 2011)
This article traces the emergence of a systematic approach to combating heresy during the Umayyad period. It argues that the Umayyads sought to silence religious dissent by labelling it as heresy and that the doctrinal boundaries of orthodoxy narrowed as the Umayyad period progressed. The article also asserts that Umayyad efforts to impose their vision of orthodoxy were an important precedent for the mihna under the Abbasids. © 2011 Society for the Medieval Mediterranean.
Keywords: Abd al-Malik; Ghaylan al-Dimashqi; Heretic; Hisham; Islam - heresy; Islamic scholar; Mabad al-Juhani; Qadariyya; Theological movement; Ummayad caliph; Ummayad caliphate; dept.his

Rosemont, jr., henry, and roger t. ames, the chinese classic of family reverence: A philosophical translation of the xiaojing - Radice, Thomas (Dao-a Journal of Comparative Philosophy, 2011)
Keywords: dept.his; peer-reviewed

The german myth of the east: 1800 to the present - Paddock, Troy R. E. (German Studies Review, 2010)
Keywords: dept.his; ⛔ No DOI found

The persistence of republicanism: class war talk, american style - Cassano, Graham; Rondinone, Troy (Labor Studies Journal, 2010)
The authors argue that there have been moments in American history when a class analysis entered into popular discourse. What has been "exceptional" about American history is the manner in which that class analysis emerged. When Americans speak the language of "class" and "class warfare," it is often clothed in the rhetoric of labor republicanism. That is, rather than offering a systemic analysis of capitalist processes, American labor republicanism offers a class analysis that sets a small set of bad acting "elites" and their dependents against the mass of American workers. The authors trace this discourse from Franklin Roosevelt's 1936 description of "economic royalists" to Lou Dobbs's nativist attack on "corporate elites" and undocumented workers. As the United States enters a new period of "class awareness" and economic crisis, this republicanism returns to haunt public discourse. © 2010 UALE.
Keywords: Franklin D. Roosevelt; Lou Dobbs; Marxian analysis; class warfare; dept.his; labor republicanism

Sinification as Limitation: Minh Mạng’s Prohibition on Use of Nôm and the Resulting Marginalization of Nôm Medical Texts - Thompson, C. Michele (Looking at it from Asia: the Processes that Shaped the Sources of History of Science, 2010)
For Vietnamese scholars in the late eighteenth and early nineteenth centuries reading and writing ability in both Chinese and Nôm (an ideographic writing system used to write Vietnamese) was considered an essential tool of scholarship and literary expression.
Keywords: Chinese Character; Imperial Examination System; Medical Text; Royal Court; Vietnamese Language; dept.his

The Folklore of Deinstitutionalization: Popular Film and the Death of the Asylum, 1973–1979 - Rondinone, Troy (Journal of American Studies, 2019)
The demise of America's state mental hospital system, or “deinstitutionalization,” has received much attention from sociologists and historians of medicine. Less understood is the manner in which the public experienced and came to terms with it. Using elements of folklore and horror studies, I will examine how popular films accommodated audiences to institutional decline and confirmed popular antistatist pessimism. The Exorcist (1973), One Flew over the Cuckoo's Nest (1975), Halloween (1978), and When a Stranger Calls (1979) helped weave a tapestry of distrust. By endorsing popular conceptions of institutional failure and presenting mythical narratives of individualist triumph, these films helped pave a path towards the conservative Reagan era to come.
Keywords: dept.his; peer-reviewed

Lovecraft Meets the Mummy: Orientalism, Race, and Monstrous Egypt in “Imprisoned with the haraohs” and “Out of the Aeons” - Rondinone, Troy (Lovecraftian Proceedings No. 3., 2019)
Keywords: dept.his; faculty_collection

The unforgettable age: young in Costa Rica of XX century - Coury Kordick, Carmen Coury (Americas, 2019)
Keywords: dept.his; peer-reviewed

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge, 2019)
Contesting the Origins of the First World War challenges the Anglophone emphasis on Germany as bearing the primary responsibility in causing the conflict and instead builds upon new perspectives to reconsider the roles of the other Great Powers. Using the work of Terrance Zuber, Sean McMeekin, and Stefan Schmidt as building blocks, this book reassesses the origins of the First World War and offers an explanation as to why this reassessment did not come about earlier. Troy R.E. Paddock argues that historians need to redraw the historiographical map that has charted the origins of the war. His analysis creates a more balanced view of German actions by also noting the actions and inaction of other nations. Recent works about the roles of the five Great Powers involved in the events leading up to the war are considered, and Paddock concludes that Germany does not bear the primary responsibility. This book provides a unique historiographical analysis of key texts published on the origins of the First World War, and its narrative encourages students to engage with and challenge historical perspectives.
Keywords: dept.his

‘Mixt marriages’: Ethnic and religious intermarriage among German-speakers in eighteenth-century Pennsylvania - McDaniel, Marie Basile (The History of the Family, 2019)
Civil and religious authorities in eighteenth-century America grew increasingly concerned over the freedom with which young people chose their marriage partners. Correlating racial, religious and cultural similarity in marriage to a stable society, these authorities attempted to limit marriage and sexual choices by requiring parental authority for marriage, distributing permits to a select few to perform marriages, and criminalizing racial miscegenation. Eighteenth-century Pennsylvania German authorities supported this attitude because they associated ethnic and religious out-marriage with the weakening of the body and the destruction of society. My study uses the marriage and birth records of eighteenth-century Pennsylvania Germans to examine their marriage and sexual relationships. I discovered that Pennsylvania Germans overwhelmingly chose to marry other German-speakers, out of proportion with their population. By examining the then available works on marriage and procreation, I discovered that Pennsylvania Germans read works that emphasized the necessity and importance of intra-ethnic and religious sex and marriage for the health of their children. Pennsylvania Germans chose their marriage partners in alignment with their community’s attitudes towards those of other ethnicities and religions. A small data set further suggests that relationships with non-Germans occurred but rarely became formalized. This complicates what we know about the sexual and emotional revolutions in the seventeenth and eighteenth centuries; far from a linear progression of attitudes towards sex, marriage, and others, eighteenth-century Pennsylvania Germans expressed multiple, contextually-driven perspectives, and in the process they created and maintained strong ethnic communities. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Defoe; German (citizen); German-speakers; Marriage; Pennsylvania; article; child; colonial; dept.his; destruction; ethnicity; female; human; human experiment; male; marriage; peer-reviewed; pre-marital; religion

Roman exempla in the early Tudor period - Kern, Darcy (English: Journal of the English Association, 2019)
Abstract. Roman exempla, or moralizing anecdotes, appear frequently in the English literature of the early Tudor period. Textual, authorial, and historical exe
Keywords: dept.his; peer-reviewed

Empire by invitation: William Walker and manifest destiny in Central America - Coury Kordick, Carmen (Americas, 2019)
Keywords: book.review; dept.his; peer-reviewed

Book Review: Viet Nam: A history from earliest times to the present. - Thompson, C. Michele (Journal of Asian Studies, 2019)
Keywords: book.review; dept.his

Boxing in the ancient world - Nakamura, Byron J. (The Cambridge Companion to Boxing, 2019)
Keywords: dept.his

The real anticommunism. Politics, gender and Cold War in Costa Rica (1948-1973) - Coury Kordick, Carmen (Americas, 2019)
Keywords: book.review; dept.his; peer-reviewed

A biography of a map in motion: Augustine Herrman's Chesapeake. - Petto, Christine M. (Journal of British Studies, 2019)
Keywords: book.review; dept.his

Beyond borders: Jean Gerson’s conciliarism in fifteenth-century Spain - Kern, Darcy (Renaissance and Reformation, 2019)
In recent years there has been renewed interest in conciliarism, the belief that the authority of the universal church resides in an ecumenical council, not the pope, though the perception remains that conciliarism had a negligible impact in Iberia. One way to better understand the evolution of conciliar thought in the Spanish kingdoms is by looking at the circulation of the works and ideas of the French conciliarist Jean Gerson (1363–1429). Though a complete reconstruction of Gerson’s circulation is impossible, one can offer an initial overview of his impact in the Spanish kingdoms not simply by counting manuscripts or incunabula, as valuable as that is, but by thinking broadly about networks of exchange and dissemination. Gerson’s works came to Spain through the church councils, trans-Pyrenees Carthusian networks, monastic reformers, printers and printing houses, mendicant reformers, and the library of the University of Salamanca. © 2019, (publisher Name). All Rights Reserved.
Keywords: dept.his; peer-reviewed

Rolf Brandt and a conservative literary journalism - Paddock, Troy RE (Literary Journalism Studies, 2019)
Rolf Brandt (1886-1953) was a German journalist, author, and political commentator. His first work was as a war reporter on the Eastern Front during the opening months of the Great War (World War I). His reports appeared in several important German newspapers (Norddeutsche Allgemeine Zeitung and Frankfurter Zeitung) and were compiled and published in 1915 as Fünf Monate an der Ostfront: Kriegsberichte (Five months on the Eastern Front: War reports). Brandt's reports were more than just army-approved press releases. He wrote in a way that constructed a bridge between the home front and the front lines. In the process he employed techniques now associated with literary journalism. With a clear point of view, he told his story through a sequence of scenes, instead of a simple historical narrative, and included genuine dialogue and status details. While scholars of German literary journalism point to Egon Erwin Kisch as the originator of German literary journalism, this study suggests Brandt should be considered an early practitioner of literary journalism in the German language. More interestingly, Brandt's particular brand of literary journalism had an unmistakably conservative nationalist perspective, thus suggesting that it is possible to have a conservative form of literary journalism. © 2019 Literary Journalism Studies. All Rights Reserved.
Keywords: Conservative literary journalism; Germany; Propaganda; Rolf Brandt; Russia; World War I; dept.his; peer-reviewed; ⛔ No DOI found

Focus introduction: Swarms, herds, and peoples—examinations of interspecies dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
As its title suggests, this Focus draws our attention to the shift in perspective brought about by environmental history, compared to the more traditional approaches of history of science. Here human knowledge of and interaction with animals are understood as part of a historically variable system that encompasses both the human realm and its environment, a system in which the various components interact and shape each other dynamically.
Keywords: dept.his; peer-reviewed; ⛔ No DOI found

Welcoming ruin: The Civil Rights Act of 1875 - Friedlander, Alan; Gerber, Richard Allan (Brill, 2018)
Keywords: dept.his

Edification through the memory of sins - Chrissidis, Nikolaos A. (Canadian-american Slavic Studies, 2018)
The article explores the practical uses of Eastern Orthodox indulgences as certificates of absolution with a dual function (as mnemonic tools and as public certificates of good standing with the church) in the early modern period. © KONINKLIJKE BRILL NV, LEIDEN, 2018
Keywords: Eastern Orthodox indulgences; Eastern Orthodox penitential practices; Mese katastasis ton psychon; Patriarch Dositheos of Jerusalem; Purgatory; Synchorochartia; dept.his; peer-reviewed

“Notorious abuse,” “traditious ignorance,” and “ambitious incroachment” in seventeenth-century Dutch, English, and French maps of North America - Petto, Christine M. (Cartographica: The International Journal for Geographic Information and Geovisualization, 2018)
In consideration of Richard Daniel’s alarmed discourse found in the text accompanying his map of the English empire in America (1679), one must investigate the supposedly offending French, English, and Dutch maps of the second half of the seventeenth century for North America and, in particular, the region of the Atlantic coastline and the rhetorical devices of possession found on or in these geographical works. In addition to looking at territorial boundaries, one should also make note of armorial bearings, ships with naval ensigns, toponyms and their placement on the territory, dedicatory cartouches, legends with geographical or historical information, native scenes, and symbols for settlement. In addition to attention to possible constraints on or from the map trade, one must consider the correspondence between colonial officials and their respective governments regarding boundaries, encroachment, sovereignty, or the need for maps with a particular focus on the North American coastline. This correspondence reflects the state’s point of view, which in turn was often manifested on maps and in geographical works. Interestingly intertwined with this outspoken sense of rightful possession were the contemporary claims from some quarters that the cartographic enterprise of the late seventeenth century now embraced an empirical approach, as well as the seemingly opposing thread of the economic realities of the print trade, which often used old copper plates with little to no cartographic revision, so that long after political, economic, or military actions resulted in an “adjustment” in possession, printed maps, atlases, and other geographical works still reflected earlier circumstances. © University of Toronto Press
Keywords: Cartography; Colonies; England; France; History; Netherlands; New England; New Netherland; North America; Seventeenth-century maps; The Netherlands; United Kingdom; colonialism; dept.his; economic history; empirical analysis; historical cartography; human settlement; peer-reviewed; seventeenth century; territorial dispute

Book Review: Labor under fire: A history of the AFL-CIO since 1979 - Rondinone, Troy (The Journal of American History, 2018)
Keywords: book.review; dept.his

War and Environment - Smith, Jason W. (The Routledge History of Global War and Society, 2018)
Scholars have offered at least four distinct but interrelated conceptual frameworks for examining the relationship between militaries and the natural world.
Keywords: dept.his

Book Review: Three roads to Magdalena: coming of age in a southwest borderland, 1880–1990 - Amerman, Stephen Kent (Ethnohistory, 2018)
Keywords: book.review; dept.his

Book Review: childbirth, maternity, and medical pluralism in French colonial Vietnam, 1880–1945 by Thuy Linh Nguyen - Thompson, C. Michele (Journal of Vietnamese Studies, 2018)
Keywords: book.review; dept.his

Translating the body - Thompson, Michele; Pols, Hans; Warner, John Harley (University of Chicago Press, 2018)
Until recently, receiving a European or North American-style medical education in Southeast Asia was a profoundly transformative experience, as western conceptions of the body differed significantly from indigenous knowledge and explanations. Further, conceptions of the human body had to be translated into local languages and related to vernacular views of health, disease, and healing. Translating the Body is the first book to present the history of biomedical education across Southeast Asia. The contributors chart and analyze the organization of western medical education in Southeast Asia, public health education campaigns in the region, and the ways in which practitioners of what came to be conceived of as “traditional medicine” in many Southeast Asian countries organized themselves in response.
Keywords: dept.his

Hope in an ad: Teaching consumerism and idealized womanhood using 1920s advertisements - Carter-David, Siobhan (Advertising & Society Quarterly, 2018)
Keywords: dept.his; peer-reviewed

Computer systems: Digital design, fundamentals of computer architecture and assembly language - Elahi, Ata (Springer International Publishing, 2018)
This textbook covers digital design, fundamentals of computer architecture, and assembly language. The book starts by introducing basic number systems, character coding, basic knowledge in digital design, and components of a computer. The book goes on to discuss information representation in computing; Boolean algebra and logic gates; sequential logic; input/output; and CPU performance. The author also covers ARM architecture, ARM instructions and ARM assembly language which is used in a variety of devices such as cell phones, digital TV, automobiles, routers, and switches. The book contains a set of laboratory experiments related to digital design using Logisim software; in addition, each chapter features objectives, summaries, key terms, review questions and problems. The book is targeted to students majoring Computer Science, Information System and IT and follows the ACM/IEEE 2013 guidelines. • Comprehensive textbook covering digital design, computer architecture, and ARM architecture and assembly • Covers basic number system and coding, basic knowledge in digital design, and components of a computer • Features laboratory exercises in addition to objectives, summaries, key terms, review questions, and problems in each chapter
Keywords: ARM architecture; ARM processors; Assembly language; Boolean algebra; Computation theory; Computer architecture; Digital designs; Digital devices; Digital television; Information representation; Laboratory exercise; Laboratory experiments; Number system; Numbering systems; Reviews; Sequential logic; Textbooks; dept.csc

Book Review: Counterpunch: the cultural battles over heavyweight prizefighting in the American west - Rondinone, Troy (The American Historical Review, 2017)
Keywords: book.review; dept.his

Confucius and filial piety - Radice, Thomas (A Concise Companion to Confucius, 2017)
Keywords: dept.his

Dreams of antiquity: H. P. Lovecraft’s great Roman dream of 1927 - Nakamura, Byron (Lovecraftian Proceedings No. 2, 2017)
This second volume of Lovecraftian Proceedings contains a wealth of cutting-edge scholarship on the dreamer from Providence, including substantial articles from both recipients of the S. T. Joshi Endowed Research Fellowship for H. P. Lovecraft at Brown University.  Lovecraftian Proceedings fosters exploration of Lovecraft as a rationalist who created an elaborate cosmic mythology, and how this mythology was influenced by, and has come to influence, numerous other authors and artists. The papers which comprise Lovecraftian Proceedings were presented during a key part of the NecronomiCon Providence convention, the Dr. Henry Armitage Memorial Symposium. TABLE OF CONTENTS Introduction             Dennis P. Quinn Dreams of Antiquity:  H. P. Lovecraft's Great Roman Dream of 1927Byron Nakamura The Poet’s Nightmare: The Nature of Things According to LovecraftSean Moreland Reordering the Universe: H. P. Lovecraft’s Subversion of the Biblical DivineRené J. Weise Resisting Cthulhu:  Milton and Lovecraft’s Errand in the Wilderness Marcello Ricciardi “The Discriminating Urban Landscapist": Tradition and Innovation in the Architectural Writings of H. P. LovecraftConnor Pitetti Tentacles in the Madhouse: The Role of the Asylum in the Fiction of H. P. LovecraftTroy Rondinone Unspeakable Languages: Lovecraft Editions in Spanish Juan L. Pérez-de-Luque Color out of Mind: Correlating the Cthulhu Mythos Universe to the Autism Disorder SpectrumLars G. Backstrom Darwin and the Deep Ones: Anthropological Anxiety in "The Shadow over Innsmouth" and Other StoriesJeffrey Shanks The “Inside” of H. P. Lovecraft’s Supernatural Horror in the Visual Arts Nathaniel R. Wallace H. P. Lovecraft’s OptimismMatthew Beach Insider, Outsider: From the Commonplace to the Uncanny in H. P. Lovecraft’s Narration and DescriptionsDaphnée Tasia Bourdages-Athanassiou H. P. Lovecraft, Georges Bataille, and the Fascination of the Formless: One Crawling Chaos Seen Emerging from Opposite ShoresChristian Roy  Ripples from Carcosa: H. P. Lovecraft, True Detective, and the Artist-InvestigatorHeather Poirier Lovecraft for the Little Ones: ParaNorman, Plushies, and MoreFaye Ringel and Jenna Randall Contributors AppendixAbstracts of Papers Presented at the Dr. Henry Armitage Memorial Scholarship Symposium,NecronomiCon Providence 20-23 August, 2015Chair: Dennis P. Quinn Index
Keywords: dept.his

Book Review: The people between the rivers: the rise and fall of a bronze drum culture, 200-750 CE - Thompson, C. Michele (Journal of Asian Studies, 2017)
Keywords: book.review; dept.his

Li (ritual) in early Confucianism - Radice, Thomas (Philosophy Compass, 2017)
Keywords: dept.his

Constructing costa rica’s inter-american highway and building U.S. empire: Social, economic, and political change at the local level, 1941-44 - Coury Kordick, Carmen (Journal of Iberian and Latin American Research, 2017)
Before 1944, countless Costa Rican travelers perished on the narrow rocky trail that traversed the 3,491 meter Cerro de la Muerte. Undaunted, between 1941 and 1944 U.S. engineers and Costa Rican workers built a 49-mile segment of the Inter-American Highway that conquered the Cerro. For many, both in the countryside and in the city, the roadway was a symbol of progress and modernization that inspired an image of the San José-centered state as a benevolent patriarch and the United States as a wealthy and generous Good Neighbor. The roadway, however, also had its detractors, namely communist labor organizers, who saw the project as a symbol of U.S. imperial exploitation that threatened Costa Rican sovereignty and harmed workers. The Communist press and labor organizers sought to mobilize highway workers and popular discontent against the roadway, but their efforts were largely ineffective. Indeed, ultimately, roadway workers, their families, and neighbors were grateful for the increased transportation and communication the roadway furnished their communities and the well-remunerated labor opportunities this transnational infrastructure provided. In sum, the roadway’s detractors failed to foster negative perceptions of the roadway as a symbol of the exploitative nature of the U.S. Empire on the ground.
Keywords: Costa Rica; Infrastructure Development; Inter-American Highway; Nation Building; U.S. Empire; World War II; dept.his

Book Review: The baptism of early Virginia: how Christianity created race: Goetz, Rebecca Anne, Baltimore, MD: Johns Hopkins University Press 240 pp., 29.95, ISBN 978-1421419817 publication date: august 2012 - McDaniel, Marie Basile (History: Reviews of New Books, 2017)
Keywords: book.review; dept.his

Popular history in the imperial empire: family magazines as actors of the German history culture 1890-1913 - Paddock, Troy (German History, 2017)
Keywords: dept.his

Ibn ʿAsākir’s peculiar biography of Khālid al-Qasrī - Judd, Steven (New Perspectives on Ibn ʿAsākir in Islamic Historiography, 2017)
Keywords: dept.his

The implications of gia truyền: Family transmission texts, medical authors, and social class within the healing community in Vietnam - Thompson, C. Michele (South East Asia Research, 2017)
In Vietnamese medicine, gia truyen ("family recipes") refers to a set of texts, primarily in chu nôm (demotic Vietnamese characters), that preserves local knowledge about how practitioners in a specific family-based medical circle could use various plants and other materia medica to cure disease. This article traces the history of the transmission of gia truyen in the 19th and 20th centuries. It suggests that prior to the 1920s, gia truyen were written anonymously to protect the author's identity in the face of the Nguyen dynasty's repression of ch? nom writing. In the 1920s, precisely at the time that hán-nôm writing was being eclipsed by education in French and quoc ngu (Romanized Vietnamese), Vietnamese medical practitioners experienced a renaissance in the writing of chu nôm gia truyen. Moreover, chu nôm writing in the gia truyen genre continued until at least the 1990s. ©SOAS University of London 2017.
Keywords: Chu nom; Colonial; Materia medica; Medical texts; Traditional medicine; Viet Nam; class; dept.his; disease treatment; historical perspective; medical geography; nineteenth century; social history; traditional knowledge; traditional medicine; twentieth century

Method mourning: Xunzi on ritual performance - Radice, Thomas (Philosophy East and West, 2017)
Keywords: dept.his

The journey from discovery to scientific change: scientific communities, shared models, and specialised vocabulary - Roe, Sarah M (International Studies in the Philosophy of Science, 2017)
Scientific communities as social groupings and the role that such communities play in scientific change and the production of scientific knowledge is currently under debate. I examine theory change as a complex social interaction among individual scientists and the scientific community, and argue that individuals will be motivated to adopt a more radical or innovative attitude when confronted with striking similarities between model systems and a more robust understanding of specialised vocabulary. Two case studies from the biological sciences, Barbara McClintock and Stanley Prusiner, help motivate the idea that sharing of models and specialised vocabulary fill the gap between discovery and scientific change by promoting the dispersal of important information throughout the scientific community. © 2017 Open Society Foundation.
Keywords: dept.his

Extended mechanistic explanations: expanding the current mechanistic conception to include more complex biological systems - Roe, Sarah M; Baumgaertner, Bert (Journal for General Philosophy of Science, 2017)
Mechanistic accounts of explanation have recently found popularity within philosophy of science. Presently, we introduce the idea of an extended mechanistic explanation, which makes explicit room for the role of environment in explanation. After delineating Craver and Bechtel’s (2007) account, we argue this suggestion is not sufficiently robust when we take seriously the mechanistic environment and modeling practices involved in studying contemporary complex biological systems. Our goal is to extend the already profitable mechanistic picture by pointing out the importance of the mechanistic environment. It is our belief that extended mechanistic explanations, or mechanisms that take into consideration the temporal sequencing of the interplay between the mechanism and the environment, allow for mechanistic explanations regarding a broader group of scientific phenomena. © 2016, Springer Science+Business Media Dordrecht.
Keywords: Complex systems; Explanation; Mechanism; Mechanistic environment; dept.his

57. Selections from Miraculous Drugs of the South, by the Vietnamese Buddhist Monk-Physician TueTinh - Thompson, C. Michele (Buddhism and medicine: An anthology of premodern sources, 2017)
Keywords: dept.his